Chemical constituents from the aerial parts of Clematis terniflora DC - Meng-Ya Chen; Zi-Han Zhu; Xin-Yu Yu; Ya-Ru Wu; Shi-Hui Qian; Zhen-Lin Li (Biochemical Systematics and Ecology, 2027)

Stratigraphy, sedimentology, and palaeoenvironment of dinosaur-bearing Upper Cretaceous Zhengyang Formation in Zhengyang Basin, Chongqing, Southwest China - Hui Dai; Jun Wang; Liang-Dong Luo; Qian-Ru Wen; Su-Chin Chang; Yu Lin; Ming Xiao; Hai Xing (Palaeoworld, 2026)

Structure and characteristics of quercetin-loaded starch nanoparticles and their surface charges for protein corona formation with gastrointestinal digestive enzymes - Yu-Ru Wu; Zhi-Yuan Yang; Shan-Dan Zhao; Dan-Yang Shen; Ya-Jun Lin; Yi-Bin Zhou; Kang Liu (Food Hydrocolloids, 2026)

TGF-β-induced autophagy in pulmonary artery endothelial cells associated with chronic thromboembolic pulmonary hypertension - Ying-Ju Lai; Yen-Lin Huang; Ching-Yen Tsai; Po-Ru Chen; Chi-Jen Chang; Yung-Hsin Yeh; Celina De Almeida; Hsao-Hsun Hsu (Journal of Molecular Medicine, 2026)

Phylogenomics of Tanypodinae (Diptera: Chironomidae) redefines relationships in Procladiini and Tanypodini and supports a new tribe - Xiu-Ru Xiao; Yi-Ni Zhang; Hai-Feng Xu; Zhi-Chao Zhang; Yu-Yi Jiang; Yan-Xin Chen; Chen-Hong Li; Bing-Jiao Sun; Fabio Laurindo da Silva; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

Characterization of phosphorylated whey protein and its hydrolytic insoluble peptide aggregates - Hui Yang; Ru Lin; Yinuo Xiao; Xuan Shang; Shanshan Bai (International Dairy Journal, 2026)

Metagenomics-guided targeted isolation and mechanistic elucidation of haloalkaliphilic bisphenol A-degrading microorganisms - Sai Yang; Kai-yan Xing; Yue-fei Tao; Jia-yu Wang; Ke-hang Liu; Meng Zhang; Xiang-ru Xu; Lin Zhu; Wei Wei (Bioresource Technology, 2026)

Accumulation, elimination and biotransformation of paralytic shellfish toxins in ark shell Anadara kagoshimensis - Zhuo-Ru Lin; Hui-Xia Geng; Sara A. Cunha; Chang Xu; Ren-Cheng Yu (Marine Pollution Bulletin, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Asymmetric introgression and reticulate evolution result from palaeoclimate-driven range dynamics of the Smilax hispida group in North and Central America - Xin-Yi Fan; Han-Yang Lin; Ya-Lu Ru; Yun-Peng Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Effects of clay jar and stainless steel fermentation on microbial succession and flavor formation in spontaneously fermented Cabernet Sauvignon wine - Fan Yang; Lin Pan; Ru Zhai; Fuqi Li; Wen Li; Kaixiong Li (Food Bioscience, 2026)

Oral self-assembled nanomedicine orchestrates hierarchical regulation of the lipid–ROS–inflammation cascade for comprehensive therapy of non-alcoholic fatty liver disease - Jia-Jian Zhang; Yin-Sheng Tan; Chen-Lei Zhang; Yan Gui; Fan-Zhi Yan; Jie Hou; Xiang-Xuan Liu; Hua Kong; Meng-Ru Guo; Yang-Feng Cui; Xian-He Lin; Tao-Tao Fan; et al. (Chemical Engineering Journal, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

Electroacupuncture-induced gut microbiota alterations correlate with FXR/FGF15 activation and metabolic improvement in hyperlipidemic rats - Huan Wu; Li Zhou; Wei Lin; Hong-xing Zhang; Zhao-qing Zhang; Xiao-fei Wang; Shi-ru Ju; Zhi-gang Liu; Fei Hu (Advances in Traditional Medicine, 2026)

Chondroitin sulfate: an environmentally friendly immune inducer enhanceing plant resistance to potato virus X and tobacco mosaic virus - Cui-Hong Hao; Wei Xu; Tian-Qi Liang; Yun-Mei Li; Yi-Lin Guan; Ru-Xin Li; Dan-Ya Ju; Chun-E Peng; Li-Zeng Peng; Qing-Bin Wang (Physiological and Molecular Plant Pathology, 2026)

Phylogenomics, reticulate evolution, and taxonomic revision of East Asian Cardamine (Brassicaceae) in the Hengduan biodiversity hotspot - Jia-lu Li; Dan-hui Liu; Jiang-lin Miao; Yi He; Liao-cheng Zhao; Di Zhang; Ke-ping Ma; Quan-ru Liu (Molecular Phylogenetics and Evolution, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Corrigendum to “Mg-doped CoCr₂O₄ nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage” [Chem. Eng. J. 535 (2026) 175200] - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Shape-memory effect in a flexible hydrogen-bonded organic framework for efficient C2H2/CO2 separation - Chunchen Gao; He Zheng; Wenjie Chen; Yiting Guo; Ru Xu; Ziyi Luo; Qifeng Luo; Xingliang Nie; Xin Lian; Xiongli Liu; Yabing He; Lin Li; et al. (Chemical Engineering Journal, 2026)

Multiomics, pharmacogenomic, and structural characterization of NCCRP1 as a candidate therapeutic target in ovarian cancer - Dahlak Daniel Solomon; Yung-Kuo Lee; Sachin Kumar; Kai-Fu Chang; Chung-Hsien Lin; Ching-Chung Ko; Ngoc Uyen Nhi Nguyen; Do Thi Minh Xuan; Neethu Palekkode; Chih-Yang Wang; Hui-Ru Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Early microbial succession and matrix destabilization guide long-term preservation of refrigerated kelp - Neng-Pai Shi; Si-Chuang Tu; Bing-Bing Wu; Ru-Meng Xiao; Hai-Bin Pan; Sheng-Nan Lin; Roger Ruan; Xue-Mei Hou; Xiang-Yang Lin (Food Chemistry, 2026)

Unraveling antibiotic fate in a highly urbanized estuary: Spatiotemporal patterns, multi-media partitioning, and contaminant prioritization - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Xiao-Ping Huang (Marine Pollution Bulletin, 2026)

Bioactive PVA/SDES propolis extracts composite films for extending oyster shelf life: Structure, functionality, and preservation performance - Tian Du; Lin-Kun Sun; Pei-Ru Zhou; Yu-Cang Zhang; Yan-Zhen Zheng (Food Packaging and Shelf Life, 2026)

Shifting carbon emission dominance across subway lifecycle phases: A refined subsystem-interaction assessment - Jing Pu; Chen Cai; Shijun Chen; Ru Guo; Ruimin Lin; Xingyu Ding; Jia Liu; Kaiming Peng; Xiangfeng Huang (Environmental Impact Assessment Review, 2026)

Constructing compatible LLZTO/PEO interfaces with fast Li+ transport channels for high-performance composite polymer electrolytes - Yimei Jin; Yiting Lin; Zekai Zhang; Bing Li; Ru Wang; Cheng Lian; Xia Han; Honglai Liu; Haiping Su; Jingkun Li (Chemical Engineering Journal, 2026)

Liquid-phase hydrogenation of benzaldehyde to benzyl alcohol over NiCoAl‑R catalysts: Synergistic metal–metal oxide interfaces for enhanced catalytic performance - Lingmei Yang; An Wei; Ru kuan Liu; Guo ling Zhang; Bing Han; Baining Lin; Lianhua Li (Journal of Environmental Chemical Engineering, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

A capillarity-engineered trilayer Janus pad-based food preservation system for directional exudate management and sustained oregano-oil delivery - Ru Li; Wanru Jin; Lin Wang; Lingling He; Xiaowei Li; Peng Wang (Chemical Engineering Journal, 2026)

Multiprotein-based nanomedicines with dual CD44/CD133 targeting and GSH-responsive drug release for improving cancer chemotherapy - Lu-Yi Yu; Pei-Wei Shueng; Yu-Hsin Wang; Yu-Wei Yen; Kuan-Wei Chen; Chieh-Ru Li; Hsin-Cheng Chiu; Yu-Wen Lin; Chun-Liang Lo (Drug Delivery and Translational Research, 2026)
Albumin, a highly biocompatible protein, has been utilized in the construction of anti-cancer drugs for the treatment of various cancers. However, albumin-based nanomedicines still face several clinical challenges, including low stability in the bloodstream, non-specific targeting ability, and lack of controlled release capability. To address these limitations, we developed a multiprotein-based nanomedicine for targeted chemotherapy of non-small cell lung cancer (NSCLC). This nanomedicine was assembled using a heart-shaped albumin and two Y-shaped anti-CD44 and anti-CD133 antibodies. To enhance stability and improve therapeutic efficacy, the multiproteins were crosslinked using disulfide bond linkers and loaded with paclitaxel and ceramide. This resulted in nanomedicines that exhibited responsiveness to glutathione (GSH) and demonstrated inhibition of tumor cancer cells and cancer stem cells (CSCs). Our experimental results indicated that the inclusion of anti-CD44 and anti-CD133 antibodies enhanced the targeting capability of nanomedicines towards cancer cells and CSCs in an in vitro study and the accumulation in both normoxic regions and hypoxic niches in in vivo tumor xenografts. The multiprotein-based nanomedicines also demonstrated GSH-dependent drug release behavior, induced apoptosis in cancer cells and CSCs, inhibited cell migration, and effectively suppressed NSCLC tumor growth. Overall, our findings presented a novel nanostructure created from differently shaped proteins for application in drug delivery. This multiprotein-based nanomedicines showed promising potential in addressing the limitations of albumin-based nanomedicines and may offer improved therapeutic outcomes for cancer treatment. Graphical Abstract

Single-cell transcriptomics reveal PRRC1 as a malignant cell enriched driver of DNA repair and therapy resistance in glioblastoma - Sachin Kumar; Ming-Cheng Tsai; Dahlak Daniel Solomon; Juan Lorell Ngadio; Do Thi Minh Xuan; Ching-Chung Ko; Hung-Yun Lin; Meng-Chi Yen; I-Jeng Yeh; Yung-Kuo Lee; Hui-Ru Lin; Jian-Ying Chuang; et al. (DNA Repair, 2026)

Rational design of one-dimensional chain-like metal-organic frameworks featuring engineered nano-pockets for highly selective and efficient uranium sequestration - Zhi Wu; Shu-Yuan Zhang; Bin Lin; An-Min Song; Fei-Yi Kong; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2026)

Mg-doped CoCr2O4 nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Characterization of a new isolate of tomato zonate spot virus from Vaccinium uliginosum L. in China - Yueyan Yin; Tao Lin; Ru Dong; Zhijiao He; Jing Zhong; Liling Zhao; Jiawei He; Ming Ding; Tingting Li (Journal of Plant Pathology, 2026)

Validation of a numerical model for seismic behavior of wind turbine nacelle components using experimental data - Wei-Hung Hsu; Bai-Yi Huang; Juin-Fu Chai; Fan-Ru Lin (Engineering Structures, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

Long-term intercropping increases soil aggregate stability by altering soil colloid content and stability - Chuan-Lin Xiao; Jing-Ru He; Cheng-Bao Wang; Wei-Ping Zhang; Jun Mao; Peter Christie; Jian-Ying Shang; Long Li (Plant and Soil, 2026)

Haladaptatus marinus sp. nov., Haladaptatus rarus sp. nov., Haladaptatus ordinarius sp. nov., and Halomicrococcus pelagicus sp. nov., halophilic archaea from diverse coastal tidal flats - Xin-Ru Zhang; Jing Hou; Zhen Rong; Yue-Hong Wu; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Manganese acts as savior rather than accomplice of antibiotic stress: Dual cycles of ROS scavenging and Mnammox - Dong-Jun Hou; Wei-Lin Guo; Qian-Ru Liu; Hong-Wei Yang; Qiu-You Xu; Yun-Fei He; Nian-Si Fan; Ren-Cun Jin (Journal of Water Process Engineering, 2026)

Exploratory analysis of epigenetic dynamics and small extracellular vesicles in Penaeus vannamei hemocytes under inactivated Vibrio parahaemolyticus priming - Yu-Ru Lin; Guan-Lin Lai; Yu-Hsuan Sun; Ta-Jeng Yang; Ting-Yu Huang; Huu-The Nguyen; Muhammad Ar Rozzaaq Nugraha; Novi Rosmala Dewi; Yeh-Fang Hu; Fan-Hua Nan (Journal of Invertebrate Pathology, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

Multi-source remote sensing for spatial mapping of salt-affected agricultural soils in Taiwan - Nguyen-Thanh Son; Chein-Hui Syu; Chi-Farn Chen; Cheng-Ru Chen; Huan-Sheng Lin; Yi-Ting Zhang; Tsang-Sen Liu; Chun-Chien Yen (Applied Geomatics, 2026)

Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

Ti(IV)-incorporated covalent organic frameworks for efficient dark-photocatalytic reduction of U(VI) - Li-Ling Chen; Cheng-Peng Niu; Rui Zhang; Yun-Peng Wu; Zhen-Wen Zhang; Bin Lin; Cheng-Rong Zhang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

In situ H2O2 generation via synergistic electro-Fenton for enhanced refractory organics removal in the landfill leachate during pre-aerobic treatment - Cong Ding; Ling-ling Lai; Ru Wang; Cai-hong Qin; Lin-jiang Yuan (Chemical Engineering Journal, 2026)

APMAP regulated by YY1 transcription mediates ferroptosis and metastasis in non-small cell lung cancer through the PI3K/AKT/mTOR pathway - Xiaohong Zhuang; Shu Lin; Cheng-sheng zhang; Qi Qin; Qixing Yan; Jing-ru Luo; Wenjun Tang (Journal of Molecular Histology, 2026)

Two new clerodane diterpenoids and their anti-inflammatory activity from Callicarpa integerrima - Muhammad Aurang Zeb; Xiao-Ying Ruan; Xing-Jie Zhang; Yu-Tong Xing; Meng-Ru Wang; Yuan-Lin Kong; Xiao-Li Li; Kai Jiang; Wei-Lie Xiao (Natural Product Research, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Spermidine carbon quantum dots as an alternative antimicrobial agent for hatcheries rearing Pacific white shrimp (Litopenaeus vannamei) - Hung-Yun Lin; Han-Tso Lin; Yun-Ru Chiang; Ya-Yun Lu; James Pan; Hou-Ju Lin; Wan-Ching Kuo; Han-Jia Lin; Han-You Lin (Aquaculture, 2026)

Near-full-component sewage sludge valorization via integrated alkali-mediated pyrolysis and sub-boiling temperature crystallization of hierarchical carbon-zeolite composites from carbonaceous and inorganic constituents - Zhihang Yuan; Houmin Yin; Jicui Cui; Changfu Yang; Zhou Zhen; Xiaohan Cui; Yumeng Jin; Lifeng Lin; Long Kong; Ruina Zhang; Ruyi Wang; Lei Che; et al. (Water Research, 2026)

Assessment of provincial PV recycling potential: Integrating product lifetime distribution and scrap capacity - Bao-Jun Tang; Wen Shi; Ru Li; Xi-Lin Cao (Sustainable Production and Consumption, 2026)

Conductive forward osmosis membranes modified with rGO-ZnO composites for improving aquaculture wastewater reclamation - Yi-Li Lin; Nai-Yun Zheng; Wan-Ru Tsai (Journal of Water Process Engineering, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Reducing the healthcare carbon footprint through fully self-service artificial intelligence-powered screening: A comparative simulation study utilizing data from Shanghai City and Lixin Town, China - Yingyan Ma; Xiyuan Shi; Lina Lu; Yi Xu; Juzhao Zhang; Tao Yu; Yajun Peng; Enren Ke; Senlin Lin; Ru Guo; Haidong Zou (Journal of Cleaner Production, 2026)

Biofilm-mediated mitigation of nitrous oxide emissions in anammox-based wastewater treatment - Zhiman Lin; Jinfan Zhang; Ru Wang; Jingmin Ou; He Zhang; Zihua Wang; Fangyuan Zheng; Xiantao Sun; Xin Wei; Yiming Huang; Zhenguo Chen; Mark C.M. van Loosdrecht; et al. (International Biodeterioration & Biodegradation, 2026)

Sustainable extraction and bioconversion of tea stems using NADES: Dual benefits in polyphenolic recovery and carbohydrates enzymatic hydrolysis - Lin-Kun Sun; Pei-Ru Zhou; Tian Du; Yu-Cang Zhang; Yan-Zhen Zheng (Food Chemistry, 2026)

Associations of particulate matter size fractions and chemical composition with conjunctivitis and eczema: epidemiological evidence from the Pearl River Delta, China - Lu-Yin Wu; Mohammed Zeeshan; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Wen-Wen Bao; Yang Zhou; Muhammad Amjad; Li-Zi Lin; Ru-Qing Liu; Zhi Wang; Guang-Hui Dong (Environmental Research, 2026)

A hydrogel-based SERS sensor with wearable potential and machine learning integration for sweat stimulant detection - Ru Liu; Xin Zhuang; Ping Lin; Luyao Lin; Jiajia Liu; Yuhua Hu; Ruiyun You; Yudong Lu (Chemical Engineering Journal, 2026)

Behaviors and adaptive strategies of anammox microbiota in response to typical ionic liquid: Metabolic compensation and gene regulation - Dong-Jun Hou; Wei-Lin Guo; Hong-Wei Yang; Qian-Ru Liu; Nian-Si Fan; Ren-Cun Jin (Bioresource Technology, 2026)

A proposed framework based on traffic volume and the design of a bottom-up methodology to estimate the CO emission of on-road vehicles - Shan-Yi Shen; Ru-Yun Chang; Yun-Wei Liao; Wei-Chun Chou; Yu-Hao Lin; Ping-Yu Liu (Atmospheric Pollution Research, 2026)

Functional spermidine-derivative carbon quantum dots (SPD-CQD) for disease control in shrimp - Han-You Lin; Yun-Ru Chiang (Fish & Shellfish Immunology, 2025)

Transcriptomic insights into neuroendocrine dysregulation in Macrobrachium rosenbergii infected by infectious precocity virus - Yun-Ru Chiang; Han-You Lin (Fish & Shellfish Immunology, 2025)

Fermented Broussonetia papyrifera leaves on growth performance, immune responses, and resistance to Vibrio of shrimp - Guan-Lin Lai; Yu-Ru Lin; Ta-Jeng Yang; Yu-Ting Chu; Fan-Hua Nan; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

Effects of feed supplementation with fermented Broussonetia papyrifera leaves on non-specific immune responses, resistance to Vibrio parahaemolyticus, growth, intestinal histology, and microbiota of white shrimp (Penaeus vannamei) - Guan-Lin Lai; Yu-Ru Lin; Ta-Jeng Yang; Yu-Ting Chu; Fan-Hua Nan; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

Natural and built environments and heart failure risk: An exposome-wide analysis in the UK Biobank - Xuewei Huang; Siyu Yin; Meng Yao; Fang Lei; Weifang Liu; Lijin Lin; Tao Sun; Yuanyuan Cao; Xingyuan Zhang; Ru Li; Liwen Wang; Yufeng Hu; et al. (Environmental Research, 2025)

Computational-assisted protein engineering to develop thermostable and highly active catalase for industrial and biocatalytic applications - Shuai Xu; Ya-min Chen; Xiang-yu Meng; Ru Pan; Ao-xuan Yan; Zhi-min Li; Zong-lin Li (Bioresource Technology, 2025)

Gut microbiome-targeted therapeutics for chronic kidney disease: comparative efficacy of probiotic and microbial preparations - Yi-Ke Li; Wen-Ru Li; Huan Ren; Chen-Lin Xiao; Zhen Guo; Jian-Quan Luo (Inflammopharmacology, 2025)

Identification of the Q-type ZFP gene family in Triticeaes and drought stress expression analysis in common wheat - Pengyan Guo; Changyan Cui; Baoquan Quan; Jiping Zhao; Jingna Ru; Yanzhen Wang; Zhiyuan Song; Aohui Lin; Shuwen He; Guanghao Wang (Genetica, 2025)

Particulate pollution in underground restaurants with increased use of prefabricated dishes: Characteristics and influential factors - Yiyun Zhuang; Almira Anwar; Zhe Li; Ru Zhang; Feng Shi; Yuehua Lin; Chen Chen; Bin Zhao (Building and Environment, 2025)

Temporal variability of greenhouse gas fluxes in monoculture of tilapia in ponds - Yi–Jung Chen; Han–Yang Yeh; Chien-Wei Tu; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; Ruei-Feng Shiu; Tzu-Ning Teng; Meng–Chou Lee; Fan–Hua Nan (Aquaculture International, 2025)

Bioactive scalarane sesterterpenoids and polybrominated diphenyl ethers from the two sponges Hippospongia sp. and Dysidea sp. - Chen You-Ying; Sung Ping-Jyun; Weng Jing-Ru; Chun-Lin Chen; Su Jui-Hsin (Phytochemistry Letters, 2025)

Chemical constituents isolated from leaves of seashore plant Aglaia rimosa - Jing-Ru Weng; Jui-Hsin Su; Ping-Jyun Sung; Wei-Yu Lin; Zhen-Hong Han; You-Ying Chen; Chun-Lin Chen (Phytochemistry Letters, 2025)

Inhibition of transforming growth factor β signaling by prodigiosin through disruption of receptor recycling and subcellular translocation in epithelial cells - Chun-Lin Chen; Jing-Ru Weng; Jui-Hsin Su; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Polycyclic aromatic hydrocarbon aggravates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease through disturbing hepatocyte sphingolipid metabolism - Hui-Ru Kuo; Yu-Fen Chung; Li-Ting Wang; Chih-Wen Wang; Shih-Hsien Hsu; Li-Chen Chen; Ming-Hong Lin; Shau-Ku Huang; Kwei-Yan Liu (Environmental Pollution, 2025)

Corrigendum to “Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices” [Chem. Eng. J. 510 (2025) 161390/CEJ 161390] - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Integrating machine learning and metabolomics to uncover new biomarkers for predicting pesticide exposure among patients with kidney function decline - Junne-Ming Sung; Yu-Chi Hung; Wan-Ru Wang; Chiau-Jun Chu; Yen-Ping Lin; Kuan-Hung Liu; Trias Mahmudiono; Hsiu-Ling Chen (Science of The Total Environment, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Genomic analysis of Pseudoalteromonas sp. SD03 reveals its potential in chitin hydrolysis - Yu-Xuan Jiang; Wen-Yue Xu; Hui Liu; Si-Qi Lin; Sha-Sha Liu; Xi-Ying Zhang; Yan-Ru Dang (Marine Genomics, 2025)

A bioluminescent enzyme immunoassay based on nanobody-nanoluciferase fusion protein for the detection of fenpropathrin - Luo-Ji Yang; Lin Luo; Ai-Fen Ou; Hao-Sheng Zheng; Ya-Ru Li; Qileng Aori; Änatoly V. Zherdev; Zhen-Lin Xu (Food Bioscience, 2025)

Anti-disintegration property of red soil treated with building gypsum powder - Yinlei Sun; Zhen Li; Xuan-Chen Lin; Qing-Ru Du; Xi Zou; Xianwei Zhang (Applied Clay Science, 2025)

Responses of plant community drought resistance and resilience to warming and nitrogen addition vary with recurrent droughts in a semi-arid grassland - Haidao Wang; Jian Song; Yongge Fan; Jianyang Xia; Lin Jiang; Qingshan Zhang; Heng Li; Jingyi Ru; Jiayin Feng; Lingjie Kong; Jiajun Zhang; Xueli Qiu; et al. (Agriculture, Ecosystems & Environment, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Antiviral prenylated C6–C3 derivatives containing a methylenedioxyl group from the roots of Illicium brevistylum - Jing-Yu Zhang; Qian-Ru Wang; Hui-Lin Yang; Rong-Mei Gao; Mi Li; Jia Yang; Yu-Huan Li; Li Li; Shuang-Gang Ma (Phytochemistry, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Transfer patterns of human blood to follicular fluid of per- and polyfluoroalkyl substances with distinct molecular structures and physico-chemical properties - Yun-Ting Zhang; Michael S. Bloom; Yang Zhou; Saif Ur Rehman; Chu Chu; Kun Zhao; Biao Yin; Zhong Lin; Yuan-Yuan Fan; Li-Zi Lin; Ru-Qing Liu; Weihong Tan; et al. (Journal of Hazardous Materials, 2025)

Unveiling a new hemocyte subpopulation in white shrimp (Penaeus vannamei) and the characterization of immune response in hemocyte subpopulation - Novi Rosmala Dewi; Ari Widodo; Muhammad Ar Rozzaaq Nugraha; Min-Da Yang; Ta-Jeng Yang; Yu-Ru Lin; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

N,O-interlocked cavity-structured functionalized metal–organic frameworks for one-step efficient removal of highly toxic thorium from tailings wastewater - An-Min Song; Zhi Wu; Bin Lin; Meng-Jie Yang; Qing Yang; Shu-Yuan Zhang; Xiao-Xing Wang; Zhi-Hai Peng; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Safranal ameliorates atherosclerosis progression partly via repressing PI3K/Akt and NF-κB signaling pathways in ApoE (−/−) mice - Yining Geng; Manping Song; Bing Huang; Ru Lin; Shiwen Wu; An Lin (Journal of Natural Medicines, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

Delineate the unknown aquifer geometry and boundary condition using hydraulic tomography - Mpendulo Mangaliso Mtsetfwa; Zaiyong Zhang; Chengcheng Gong; Hong-Ru Lin; Jet-Chau Wen; Yu-Li Wang (Journal of Hydrology, 2025)

Strategic carbon source supplementation enhances nitrite degradation by Pantoea sp. A5 in variable temperature conditions - Tzu-Yuan Sung; Anil Kumar Patel; Shang-Ru Lin; Chuan-Ting Huang; Ying-Tang Huang (Bioresource Technology, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Mitigating low-temperature frost damage in Taiwan high-altitude tea cultivation: physiological insight and protective strategies - Po-Heng Chen; Ru-Hong Lin; Chui-Feng Chiu; Yu-Sheng Lin (Planta, 2025)

Toxicity and Safety Assessment of Key Pesticides Used in Rice Fields on Rice Flower Carp (Procypris merus) - Qianxue Shao; Yongming Ruan; Ru Liang; Ruixin Jin; Zhixi Jin; Lin Xie; Yongqing Chi; Jiaojiao Xia; Pingyang Zhu (Fishes, 2025)
Integrated rice–fish farming, crucial for sustainable agriculture, relies on the judicious use of pesticide. This study evaluates the toxicity of six common rice-field pesticides on Procypris merus (rice flower carp), a key species in these systems. We conducted acute and chronic toxicity tests, assessing survival, growth, oxidative stress (SOD, CAT, MDA, 8-OHdG), and neurotoxicity (AChE). Results revealed a spectrum of toxicity: abamectin and trifloxystrobin were highly toxic; pretilachlor was moderately so; and glufosinate-ammonium, triflumezopyrim, and thiazole zinc were low. Notably, triflumezopyrim induced significant oxidative stress and DNA damage, while all three low-toxicity pesticides inhibited AChE activity, indicating potential neurotoxicity. Despite these effects, all observed toxicities were reversible within 7–14 days. Considering that the tested concentrations exceeded typical field application rates, glufosinate-ammonium, triflumezopyrim, and thiazole zinc are deemed relatively safe for P. merus at recommended dosages. Our findings provide critical insights for optimizing pesticide selection in rice–fish farming, balancing pest control with ecological safety, thereby informing sustainable agricultural practices.

Calculation and analysis of wave loads and hydrodynamic coefficients on submerged floating tunnels with various cross-sections - Hong-Fei Mao; Wei-Jiang Zheng; Qin-Ru Yang; Zhong-Bing Zhou; Zheng-Lin Tian; Long Han; Guang-Lin Wu; Jin-Bo Lin (Ocean Engineering, 2025)

Collagenases from hepatopancreas and muscle of Litopenaeus vannamei: Purification, characterization and comparison of their behaviors in collagen degradation - Xu-Chen Xiao; Jia-Yin Huang; Yu-Lei Chen; Kai-Yuan Cao; Ru-Qing Yang; Duan-Quan Lin; Shu-Jun Hong; Yu-Ting Yang; Min-Jie Cao (Food Chemistry, 2025)

Chlorinated paraffins exposure in particulate matter increase the risk of attention-deficit/hyperactivity disorder symptoms in children and adolescents - Wan-Ting He; Jing-Wen Huang; Yun-Ting Zhang; Edwin Trevathan; Zhengmin Qian; Ri'enna Boyd; Michael Elliott; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Guang-Hui Dong (Environmental Pollution, 2025)

Enhancing color conversion of perovskite quantum dot-based micro-light-emitting diodes via electrochemical etching and flow chemistry system - Wen-Tse Huang; Yen-Huei Lin; Po-Yi Tu; Loan Thi Ngo; Wei-Cheng Chen; Kai-Ling Liang; Yen-Hsiang Fang; Chaochin Su; Ru-Shi Liu (Chemical Engineering Journal, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Ribosomal protein S3A (RPS3A), as a transcription regulator of colony-stimulating factor 1 (CSF1), promotes glioma progression through regulating the recruitment and autophagy-mediated M2 polarization of tumor-associated macrophages - Liang Zhang; Kun Wang; Fei Li; Lingxue Zhang; Lin Wu; Ru Tie; Kamulan Litifu; Yujie Fu; Simeng Liu; Jiaxin Ni; Pan Chang; Jun Xu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Corrigendum: Deciphering the influence of dietary synbiotics in white shrimp gut and its effects in regulating immune signaling pathways - Sofia Priyadarsani Das; Zaenal Abidin; Huai-Ting Huang; Yu-Ru Lin; Chih-Yang Huang; Yu-Sheng Wu; Yeh-Fang Hu; Fan-Hua Nan (Frontiers in Marine Science, 2025)

Quantitational life cycle assessment of Effluent-Energy-Carbon synergies and trade-offs in drinking water treatment plant upgrades - Yumeng Zhang; Zongqi Ding; Zewei Lin; Shoubin Chen; Shunjian Cheng; Kaiming Peng; Ru Guo; Xiangfeng Huang; Chen Cai; Jia Liu (Journal of Water Process Engineering, 2025)

Metallization-mediated charge transfer in cocrystals for efficient photocatalytic decontamination of mustard-gas simulant - Li Zhang; Xiao-Lin Liu; Chen Sun; Yu-Ting Luo; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2025)

Granular ferric hydroxide adsorption as a pretreatment to achieve phosphorus reclamation and high water-recovery wastewater effluent desalination - Hao Huang; Ru Liu; Mangut Sunday Jikmyan; Shihong Lin; Oded Nir; Roy Bernstein (Chemical Engineering Journal, 2025)

Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Multi-Omics Exploration of Obesity Biomarkers in Sedentary and Weight Loss Cohorts - Hui Wang; Yixiao Zhuang; Rong Hua; Ting Yao; Kaiqing Lin; Yitao Zhang; Rui Huang; Ruwen Wang; Shanshan Guo; Qiwei Shen; Yikai Shao; Wei Wu; et al. (Phenomics, 2025)

Leveraging Deep Learning to Extract Raindrop Size Gamma Distribution Parameters from Wind Profile Radar Data - Yu Huang; Zhiqun Hu; Lin Li; Ru Zhou; Xu Lu; Mengyu Huang (Journal of Meteorological Research, 2025)

Associations between lifestyle factors, physiological conditions, and epigenetic age acceleration in an Asian population - Yu-Ru Wu; Wan-Yu Lin (Biogerontology, 2025)
Epigenetic clocks use DNA methylation (DNAm) levels to predict an individual’s biological age. However, relationships between lifestyle/biomarkers and epigenetic age acceleration (EAA) in Asian populations remain unknown. We here explored associations between lifestyle factors, physiological conditions, and epigenetic markers, including HannumEAA, IEAA, PhenoEAA, GrimEAA, DunedinPACE, DNAm-based smoking pack-years (DNAmPACKYRS), and DNAm plasminogen activator inhibitor 1 level (DNAmPAI1). A total of 2474 Taiwan Biobank (TWB) individuals aged between 30 and 70 provided physical health examinations, lifestyle questionnaire surveys, and blood and urine samples. Partial correlation analysis (while adjusting for chronological age, smoking, and drinking status) demonstrated that 29 factors were significantly correlated with at least one epigenetic marker (Pearson’s correlation coefficient | r |> 0.15). Subsequently, by exploring the model with the smallest Akaike information criterion (AIC), we identified the best model for each epigenetic marker. As a DNAm-based marker demonstrated to predict healthspan and lifespan with greater accuracy, GrimEAA was also found to be better explained by lifestyle factors and physiological conditions. Totally 15 factors explained 44.7% variability in GrimEAA, including sex, body mass index (BMI), waist-hip ratio (WHR), smoking, hemoglobin A1c (HbA1c), high-density lipoprotein cholesterol (HDL-C), creatinine, uric acid, gamma-glutamyl transferase (GGT), hemoglobin, and five cell-type proportions. In summary, smoking, elevated HbA1c, BMI, WHR, GGT, and uric acid were associated with more than one kind of EAA. At the same time, higher HDL-C and hemoglobin were related to epigenetic age deceleration (EAD). These findings offer valuable insights into biological aging.

Molecular characterization of a novel mycovirus from Curvularia lunata in China - Bin Ke; Xiaohan Mo; Mengting Wu; Lin Wang; Ru Peng; Yuwen Lu; Jiejun Peng; Shaofei Rao; Guanwei Wu; Jianping Chen; Fei Yan; Hongying Zheng (Archives of Virology, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Effect of vacuum frying on the structure and bioactivity of proanthocyanidins in Chinese quince (Chaenomeles sinensis Koehne) fruit - Yu Lou; Xu Fang; Zi-Cheng Yang; Jia-Lin Fei; Yu-Ru Feng; Zhao Qin; Hua-Min Liu; Yu-Xiang Ma; Xue-De Wang (Food Chemistry, 2025)

Exploration of the impact of different drying methods on the quality of Gastrodia elata: A study based on drying kinetics and multidimensional quality evaluation - Ming-xuan Li; Bin Wang; Yu Li; Xin-ru Nie; Jing Mao; Qiang Guo; Nuo Xu; Rao Fu; Zhi-jun Guo; Xiao-li Zhao; Zhen-hua Bian; Tu-lin Lu; et al. (Food Chemistry, 2025)

One-step open-ring strategy for constructing sandwich-like metal–organic framework with highly selective removal of thorium - Meng-Jie Yang; An-Min Song; Qing Yang; Zhi Wu; Bin Lin; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Data imbalance causes underestimation of high ozone pollution in machine learning models: A weighted support vector regression solution - Ling Zhen; Baihua Chen; Lin Wang; Lin Yang; Wei Xu; Ru-Jin Huang (Atmospheric Environment, 2025)

Crop diversity significantly enhances soil carbon sequestration via alleviating soil inorganic carbon decline caused by rhizobium inoculation - Chuan-Lin Xiao; Nai-Hao Ji; Ping Wang; Jing-Ru He; Xiang Wang; Long Li (Soil and Tillage Research, 2025)

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

Self-driven electrochemical system for struvite and energy recovery from digested wastewater: Device optimization strategy and long-term operation - Yi-fan Niu; Ting-ting Dong; Zhi-guo Zhao; Meng-Yu Liu; Ru Wang; Lin-jiang Yuan (Journal of Environmental Management, 2025)

Leveraging Bio-Waste onion skin for High-Performance triboelectric nanogenerators - Po-Yen Chang; Ting-Ying Huang; Chien-Hung Yang; Chia-Hsien Lee; Ru-Jong Jeng; Chih-Ping Chen; Meng-Fang Lin (Chemical Engineering Journal, 2025)

Rhizobium inoculation improves yield advantages and soil Olsen phosphorus by enhancing interspecific facilitation in intercropping - Jun Mao; Ping Wang; Chuan-Lin Xiao; Jin-Pu Wu; Wei-Ping Zhang; Jing-Ru He; Hans Lambers; Long Li (Plant and Soil, 2025)

The Interplay Between Accumulation of Amyloid-Beta and Tau Proteins, PANoptosis, and Inflammation in Alzheimer’s Disease - Xianbo Zhuang; Jie Lin; Yamin Song; Ru Ban; Xin Zhao; Zhangyong Xia; Zheng Wang; Guifeng Zhang (NeuroMolecular Medicine, 2024)

Design and experimental analysis of real-time detection system for The seeding accuracy of rice pneumatic seed metering device based on the improved YOLOv5n - He Xing; Yikai Wan; Peng Zhong; Junjiang Lin; Mingtao Huang; Ru Yang; Ying Zang (Computers and Electronics in Agriculture, 2024)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Enhancing natural carbon sinks: Simulation of land use change under different carbon market scenarios by developing an ANN-ABM model - Ruimin Lin; Ru Guo; Yunyang Li; Guanghui Shao; Yuhao Zhang; Kaiming Peng; Xiangfeng Huang (Resources, Conservation and Recycling, 2024)

Estimating monthly NO2, O3, and SO2 concentrations via an ensemble three-stage procedure with downscaled satellite remote sensing data and ground measurements - Chu-Chih Chen; Yin-Ru Wang; Fu-Cheng Wang; Yi-Shiang Shiu; Chang-Fu Wu; Tang-Huang Lin (Journal of Hazardous Materials, 2024)

Discovery of a polyurethane-degrading enzyme from the gut bacterium of plastic-eating mealworms - Jiakang Ru; Xuan Chen; Xuena Dong; Lin Hu; Jianli Zhang; Yu Yang (Journal of Hazardous Materials, 2024)

A novel hybrid variable cross layer-based machine learning model improves the accuracy and interpretation of energy intensity prediction of wastewater treatment plant - Yucheng Li; Chen Cai; Erwu Liu; Xiaofeng Lin; Ying Zhang; Hongjing Chen; Zhongqing Wei; Xiangfeng Huang; Ru Guo; Kaiming Peng; Jia Liu (Journal of Environmental Management, 2024)

A loss-of-function mutation in OsTZF5 confers sensitivity to low temperature and effects the growth and development in rice - Limin Wang; Ru Wang; Xin Cai; Huiqi Zheng; Yuxing Huang; Yuechen Li; Mingyue Cui; Mingli Lin; Huiwu Tang (Plant Molecular Biology, 2024)

A review of urinary HPV testing for cervical cancer management and HPV vaccine surveillance: rationale, strategies, and limitations - Lin Cheng; Ru Wang; Jing Yan (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Targeting PADI2 as a potential therapeutic strategy against metastasis in oral cancer via suppressing EMT-mediated migration and invasion and CCL3/5-induced angiogenesis - Shih-Kai Hung; Chih-Chia Yu; Hon-Yi Lin; Wen-Yen Chiou; Moon-Sing Lee; Ru-Inn Lin; Ming-Chi Lu (Clinical & Experimental Metastasis, 2024)

KLK7, KLK10, and KLK11 in Papillary Thyroid Cancer: Bioinformatic Analysis and Experimental Validation - Tao Ni; Ru-hua Zhao; Jing-fang Wu; Chao-you Li; Gang Xue; Xu Lin (Biochemical Genetics, 2024)

Devosia lacusdianchii sp. nov., an attached bacterium inhibited by metabolites from its symbiotic Microcystis - Qing-Lin Deng; Yao Xiao; Ru Jia; Xin Xie; Le Wang; Xin Wang; Jian-Yuan Yang; Qi-Gen Guo; Bing-Huo Zhang (Antonie van Leeuwenhoek, 2024)

Revisiting the impact of temperature on ground-level ozone: A causal inference approach - Baihua Chen; Ling Zhen; Lin Wang; Haobin Zhong; Chunshui Lin; Lin Yang; Wei Xu; Ru-Jin Huang (Science of The Total Environment, 2024)

Electrospun film polyvinyl alcohol/chitosan loaded with cinnamon essential oil and inhibitory effects on polyphenol oxidase and dominant spoilage bacteria from Pacific white shrimp - Minzhen Zhang; Lin Wang; Xiaoyu Zou; Ru Song (Food Hydrocolloids, 2024)

Long-term exposure to ozone and sleep disorders in children: A multicity study in China - Zhao-Huan Gui; Joachim Heinrich; Lidia Morawska; Tian-Yu Zhao; Steve Hung-Lam Yim; Xiang-Qian Lao; Meng Gao; Duo-Hong Chen; Hui-Min Ma; Li-Zi Lin; Ru-Qing Liu; Guang-Hui Dong (Environmental Research, 2024)

Dissect the association between per- and polyfluoroalkyl substances (PFAS) and kidney function from the perspective of lipid molecules - Yi-Ran Chen; Shao-Bin Lin; Jia-Yun Lv; Yan Wu; Wen-Ru Feng (Environmental Pollution, 2024)

Nickel sulfide nanorods encapsulated in Nitrogen-Doped carbon on nickel foam in situ derived from Saccharomycetes cerevisiae for the selective oxidation of biomass - Hao Chen; Si-Ru Chen; Qing Yang; Le-Xing You; Qun-Feng Ye; Ai-Jun Wang; Dong-Hai Lin; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2024)

Most appropriate nozzle of six-rotor UAV for prescribed spraying liquid in tea plantation under effects of downwash flow structure in hover - Nai-Hong Hu; Wen-Xuan Zhou; Lin Zhu; Yan-Cheng Li; Xin-Yu Xie; Ru-Yan Hou; Cheng-Long Yin (Crop Protection, 2024)

Ubiquity and ecological risks of conjugated steroids cannot be overlooked: First evidence from estuarine sediments - Fei Tian; Shan Liu; Ru Xu; Nian-Nian Wu; Shuang-Shuang Liu; Yuan-Yue Cheng; Qian Xiong; Zhen-Zhao Tang; Lin-Bao Zhang; Zhe Zhang; Hai-Gang Chen (Marine Pollution Bulletin, 2024)

Neurotoxicity of fine and ultrafine particulate matter: A comprehensive review using a toxicity pathway-oriented adverse outcome pathway framework - Shuang-Jian Qin; Qing-Guo Zeng; Hui-Xian Zeng; Shen-Pan Li; John Andersson; Bin Zhao; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Nan-Xiang Jin; Mo Yang; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Comparative study on dynamic in vitro digestion characteristics of lotus seed starch-EGCG complex prepared by different processing methods - Wenjing Chen; Ru Jia; Lu Liu; Wanyi Lin; Zebin Guo (Food Chemistry, 2024)

Plantago asiatica seed as a protective agent for mitigating metals toxicity on Penaeus vannamei - Zhen-Hao Liao; Yeh-Fang Hu; Wen-Shao Wu; Huu-The Nguyen; Sofia Priyadarsani Das; Huai-Ting Huang; Yu-Ru Lin; Po-Tsang Lee; Fan-Hua Nan (Fish & Shellfish Immunology, 2024)

Mitigating thermal burden and enhancing minor phase emission energy transfer in perovskite by introducing dopamine-mediated silver nanoparticles - Zhen-Li Yan; Jhih-Yuan Chang; Chieh Tsao; Meng-Xiu Fang; Bi-Hsuan Lin; Jia-Hau Tsai; Mei-Hsin Chen; Ru-Jong Jeng; Chi-Ching Kuo (Chemical Engineering Journal, 2024)

Chemical constituents from Ficus tikoua and chemotaxonomic significance - Han-Lei Wang; Jing Lu; Xue-Lin Chen; Ru Li; Kun Zhang; Yu-Ling Guo; Xia Zhao; Yu-Mei Zhang (Biochemical Systematics and Ecology, 2024)

Ingenane-type diterpenoids inhibit non-small cell lung cancer cells by regulating SRC/PI3K/Akt pathway - Xin-Ye Wang; Yu-Jue Wang; Zi-Lin Hou; Bo-Wen Guo; Ru-Qi Wang; Qingbo Liu; Guo-Dong Yao; Shao-Jiang Song (Natural Product Research, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Magnetic conjugated microporous polymer for rapid extraction and sensitive analysis of environmental endocrine disruptors in environmental waters and dairy products - Hai-Long Jiang; Fu-Shuai Kang; Ye-Fei Fan; Xia Wang; Yun-Liang Lin; Lu Liu; Wei Liu; Yan-Fang Zhao; Ru-Song Zhao (Analytica Chimica Acta, 2024)

Bacterial functions are main driving factors on paddy soil organic carbon in both surface soil and subsoil - Xiang-Wen Huang; Jia-Jun Lin; De-Jin Li; Xiang-Qi Huang; Qi-Huan Xie; Sheng-Gang Pan; Xiang-Ru Tang; Jian-Ying Qi (Agriculture, Ecosystems & Environment, 2024)

Refining metallic nano-copper by electron-rich black carbon for superior Fenton-like catalysis in water purification: The capacitive regulation of corrosive electron transfer - Lu Zhao; Xing-Bo Chen; Xin-Ru Hu; Lei Chen; Shun Feng; Ai-Yong Zhang; Shu-Chuan Peng; Zhi-Xian Lin; Chu Jiang; Wei Da; Qi-Xin Wei (Journal of Hazardous Materials, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Thiophene-containing conjugated polymers modified Zn0.5Cd0.5S inorganic/organic S-scheme heterojunction for boosting photocatalytic hydrogen production coupled with benzyl alcohol oxidation - Lele Wei; Ru Song; Jiarui Song; Yaping Li; Yina Nie; Lin Liu; Jun Wan (Chemical Engineering Journal, 2024)

Biofunctionalized hydrogel composed of genipin-crosslinked gelatin/hyaluronic acid incorporated with lyophilized platelet-rich fibrin for segmental bone defect repair - Er-Yuan Chuang; Yi-Cheng Lin; Yu-Min Huang; Chih-Hwa Chen; Yi-Yen Yeh; Lekha Rethi; Yu-Jen Chou; Pei-Ru Jheng; Jen-Ming Lai; Chang-Jung Chiang; Chin-Chean Wong (Carbohydrate Polymers, 2024)

A comprehensive review of matcha: production, food application, potential health benefits, and gastrointestinal fate of main phenolics - Jian-Hui Ye; Qi-Ting Fang; Lin Zeng; Ru-Yi Liu; Lu Lu; Jun-Jie Dong; Jun-Feng Yin; Yue-Rong Liang; Yong-Quan Xu; Zhong-Hua Liu (Critical Reviews in Food Science and Nutrition, 2024)

Glucoconjugated monoterpene indole alkaloids with xanthine oxidase inhibitory activity from Ophiorrhiza japonica - Bao-Bao Shi; Fan Xu; Guang-Ru Zhang; Yu He; Qing Liu; Meng-Lin Feng; Zheng-Hui Li; Ji-Kai Liu (Phytochemistry, 2024)

Effects of Taiwanese indigenous cinnamon (Cinnamomum osmophloeum) leaf hot-water extract on nonspecific immune responses, resistance against Vibrio parahaemolyticus, nonviable cells, and haemocyte subpopulations in white shrimp (Penaeus vannamei) - Muhammad Ar Rozzaaq Nugraha; Yu-Ru Lin; Novi Rosmala Dewi; Huai-Ting Huang; Fan-Hua Nan; Yeh-Fang Hu (Fish & Shellfish Immunology, 2024)

Influence of electrodeposition-dealloying and silver nanoparticles on the electrochemical properties of nanoporous NiO films for supercapacitor - Ru Lin; Jiaqing Zhang; Qingshan Lu (Chemical Engineering Journal, 2024)

Enhancing open-circuit voltage and suppression of energy loss in ternary organic photovoltaics utilizing carbazole/bicarbazole-based guest donors - Chun-Yu Lin; Bing-Huang Jiang; Pei-Jui Weng; Yu Hsuan Lin; Yu-Wei Su; Hui-Shan Shih; Zhong-En Shi; Yan-Ru Lin; Jijitha Vailassery; Shih-Sheng Sun; Chih-Ping Chen; Yuan Jay Chang (Chemical Engineering Journal, 2024)

Comprehensive analysis of metal(loid)s and associated metal(loid) resistance genes in atmospheric particulate matter - Xiu-Peng Liang; He-Jing Wang; Jie-Ru Zheng; Xiao-Ru Wang; Dao-Ming Lin; Ya-Qing Wu; Rui-Lian Yu; Gong-Ren Hu; Yu Yan (Science of The Total Environment, 2024)

Upcycling of waste polycarbonate to recyclable Poly(carbonate-imines) with exceptional thermal properties and unprecedented flame retardancy - Yi-Chun Chen; Pin-Qi Mu; Kamani Sudhir K. Reddy; Ru-Jong Jeng; Mahdi M. Abu-Omar; Ching-Hsuan Lin (Chemical Engineering Journal, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Genome-wide identification of the SAUR gene family and screening for SmSAURs involved in root development in Salvia miltiorrhiza - Wei Wang; Yuwei Zheng; Lin Qiu; Dongfeng Yang; Ziyang Zhao; Yuanyuan Gao; Ru Meng; Hongguang Zhao; Shuncang Zhang (Plant Cell Reports, 2024)

Cysteine and glycine-rich protein 2 is crucial for maintaining the malignant phenotypes of gliomas through its action on Notch signalling cascade - Lingtong Liu; Fei Li; Lingxue Zhang; Yingying Cheng; Lin Wu; Ru Tie; Xiaobing Jiang; Wenwen Gao; Bochuan Liu; Yao Wei; Pan Chang; Jun Xu; et al. (Toxicology and Applied Pharmacology, 2024)

Polymer composite membranes as SERS substrate materials: Recyclable and highly stable - Haonan Wang; Chuyi Wang; Qingling Nie; Ru Liu; Yixuan Yang; Jiayi Lin; Bohan Zhang; Ruiyun You; Yunzhen Liu; Xiufeng Xiao; Yudong Lu (Chemical Engineering Journal, 2024)

Cadmium Treatment Affected the Growth and Physiology of Larix Olgensis Seedlings, the Chemical Properties of Haplic Cambisols and Toxicity Threshold Determination - Haixia Wang; Kunshu Yao; Jiaxin Ru; Jiagui Guo; Ding Liu; Yunlong Liu; LingYun Bai; Jixiang Lin; Chengbo Gu; Jinfeng Song (Journal of Soil Science and Plant Nutrition, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Candidate gene mining of GA-mediated regulation of pear fruit shape - Zeyu Xue; Ru Yang; Yadong Wang; Yuchen Ma; Yujing Lin; Zhengao Li; Yuqin Song; Xinxin Feng; Liulin Li (Horticulture, Environment, and Biotechnology, 2024)

Panax quinquefolius saponins and panax notoginseng saponins attenuate myocardial hypoxia-reoxygenation injury by reducing excessive mitophagy - Junyan Xia; Cong Chen; Yanan Sun; Sinai Li; Yuxuan Li; Bai-Ru Cheng; Yanting Pang; Yan Li; Dong Li; Qian Lin (Cell Biochemistry and Biophysics, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Potential roles of hydroxybenzoate paralytic shellfish toxins in modulating toxin biokinetics in scallops - Zhuo-Ru Lin; Hui-Xia Geng; Ren-Cheng Yu (Journal of Hazardous Materials, 2024)

Anhydride esterification to regulate water migration and reduce ice crystal formation in κ-carrageenan gel during freezing - Xinwei Xu; Feng Jiang; Kuncheng Lin; Jingjing Fang; Fuquan Chen; Yi Ru; Huifen Weng; Qiong Xiao; Qiuming Yang; Anfeng Xiao (Food Hydrocolloids, 2024)

Differentiation of closely-related species within Acinetobacter baumannii-calcoaceticus complex via Raman spectroscopy: a comparative machine learning analysis - Xue-Song Xiong; Lin-Fei Yao; Yan-Fei Luo; Quan Yuan; Yu-Ting Si; Jie Chen; Xin-Ru Wen; Jia-Wei Tang; Su-Ling Liu; Liang Wang (World Journal of Microbiology and Biotechnology, 2024)

Exercise-induced microbial changes in preventing type 2 diabetes - Ting Yao; Hui Wang; Kaiqing Lin; Ruwen Wang; Shanshan Guo; Peijie Chen; Hao Wu; Tiemin Liu; Ru Wang (Science China Life Sciences, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Carbon emissions of urban rail transit in Chinese cities: A comprehensive analysis - Jing Pu; Chen Cai; Ru Guo; Jiangchuan Su; Ruimin Lin; Jia Liu; Kaiming Peng; Chaoguang Huang; Xiangfeng Huang (Science of The Total Environment, 2024)

Trophic transfer of micro- and nanoplastics and toxicity induced by long-term exposure of nanoplastics along the rotifer (Brachionus plicatilis)-marine medaka (Oryzias melastigma) food chain - Xuan Li; Yuqi Zheng; Lin Lu; Junho Eom; Shaoguo Ru; Yuejiao Li; Jun Wang (Environmental Pollution, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Quantitative analysis of infectious precocity virus load and stunted growth syndrome via an immunohistochemical assay and reverse transcriptase quantitative real-time PCR in Macrobrachium rosenbergii - Yun-Ru Chiang; Ya-Yun Lu; Han-You Lin (Aquaculture, 2024)

Lower-bound shakedown solutions for transportation infrastructures subjected to moving harmonic loads: A focus on saturated subgrade support - Yuanxiang Lin; Jun-Jie Zheng; Hao Fang; Ru-Yi Hou; Yifan Guo (Transportation Geotechnics, 2024)

Migration of phosphorus in pig manure during pyrolysis process and slow-release mechanism of biochar in hydroponic application - Ru-Qing Jiang; Guang-Wei Yu; Lin-Hui Yu; Yu Wang; Chang-Jiang Li; Zhen-Jiao Xing; Xi-Mei Xue; Yin Wang; Cheng Yu (Science of The Total Environment, 2024)

Relationship of single and co-exposure of per-and polyfluoroalkyl substances and their alternatives with uric acid: A community-based study in China - Li-Xia Liang; Li-Zi Lin; Mohammed Zeeshan; Yang Zhou; Yong-Xiang Tang; Chu Chu; Yun-Ting Zhang; Ru-Qing Liu; Wenru Feng; Guang-Hui Dong (Journal of Hazardous Materials, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Influence on the volatilization of ethyl esters: Nonnegligible role of long-chain fatty acids on Baijiu flavor via intermolecular interaction - Qing-Ru Liu; Xian-Li Lin; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Xiao-Juan Zhang; Zheng-Hong Xu (Food Chemistry, 2024)

Adaptive shifts in plant traits associated with nitrogen removal driven by phytoremediation strategies in subtropical river restoration - Yu Xin; Lin Liu; Xiao-Ru Yang; Le-Yang Yang; Shan-Bin Guang; Yu-Ming Zheng; Quan-Bao Zhao (Water Research, 2024)

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

The associations of secondhand smoke exposure with neurodevelopmental disorders and critical time window identification: A systematic review and meta-analysis - Xiao-Xuan Ou; Xin Wang; Xiao-Ling Zhan; Shu-Li Shen; Shamshad Karatela; Jin Jing; Li Cai; Ru-Qing Liu; Li-Zi Lin; Guang-Hui Dong (Science of The Total Environment, 2024)

Low-temperature fabrication of potassium single-atom solid base catalysts with high activity in transesterification - Xiang-Bin Shao; Xing-Ru Song; Song-Song Peng; Xiao-Qin Zheng; Shi-Chao Qi; Peng Tan; Xiao-Qin Liu; Lin-Bing Sun (Chemical Engineering Journal, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

Waterlogging influences the physiology index and antioxidant enzyme activity in Cucurbita maxima and Cucurbita moschata - Kuan-Hung Lin; Shi-Peng Chen; Yi-Ru Su; Yi-Heng Tsai; Hsin-Hung Lin (Horticulture, Environment, and Biotechnology, 2024)

Deciphering the influence of dietary synbiotics in white shrimp gut and its effects in regulating immune signaling pathways - Sofia Priyadarsani Das; Zaenal Abidin; Huai-Ting Huang; Yu-Ru Lin; Chih-Yang Huang; Yu-Sheng Wu; Yeh-Fang Hu; Fan-Hua Nan (Frontiers in Marine Science, 2024)
The health of the host is significantly influenced by the gut microbiota. Penaeus vannamei (white shrimp) is one of the most profitable aquaculture species globally. Synbiotics are typically used as a beneficial diet supplement for raising aquaculture species’ growth capacities and enhancing immunity against pathogenicity. However, the effects of synbiotics on the white shrimp intestinal microbiota remain poorly understood. In the present study, we targeted the V3–V4 region of 16S rRNA genes to analyze the effects of synbiotics on white shrimp gut microbiota. Dietary synbiotics, having Lactobacillus acidophilus , and Moringa oleifera leaf extract were added to the white shrimps’ feed in various proportions in the present study. In total, 490 operational taxonomic units yielding 23 phyla, 41 classes, 94 orders, 151 families, and 250 genera of microorganisms were obtained. The diet containing L. acidophilus at 1 × 10 7 CFU/g and M. oleifera at 2.5 g/kg led to an increase in the relative abundance of beneficial microorganisms through a significant decrease in the α diversity. Moreover, it upregulated several physiological pathways such as carbohydrate metabolism, signal transduction, lipid metabolism, nucleotide metabolism, amino acid metabolism, and environmental adaptation, which led to the upregulation of the AMPK, MAPK, P13K-Akt, lysosome, peroxisome, and ferroptosis signaling pathways; this enhanced growth and immunity in white shrimp. Whether a single species or a combination of different microorganisms improves growth and immunity remains unclear till now. Nevertheless, our results will facilitate further in-depth investigation into beneficial microbial communities for upliftment of white shrimp aquaculture.

Circular economy strategies in supply chains, enhancing resource efficiency and sustainable development goals - Jing Qi Gao; Ding Li; Guang Hui Qiao; Qiao Ran Jia; Shi Ru Li; Han Lin Gao (Environmental Science and Pollution Research, 2024)

Effects of Different Intensities and Wavelengths of Light on the Growth of Juvenile Tridacna noae - Rod Ping-Tsan Lee; Yu-Ru Lin; Chih-Yang Huang; Fan-Hua Nan (Molluscan Research, 2024)

The application of static digestive models simulating the digestion system of infants and young children for the development of accessory food: Current status and future perspective - Jing Lin; Caiyu Liu; Ru Bai; Jinzhu Pang; Junan Li; Chi Zhang; Xinqi Liu; He Li; Sumei Hu (Trends in Food Science & Technology, 2024)

Soil microbial diversity and network complexity drive the ecosystem multifunctionality of temperate grasslands under changing precipitation - Changchun Zhai; Lili Han; Chao Xiong; Anhui Ge; Xiaojing Yue; Ying Li; Zhenxing Zhou; Jiayin Feng; Jingyi Ru; Jian Song; Lin Jiang; Yunfeng Yang; et al. (Science of The Total Environment, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

The apple lipoxygenase MdLOX3 positively regulates zinc tolerance - Guo-Lin Chen; Da-Ru Wang; Xin Liu; Xun Wang; Hao-Feng Liu; Chun-Ling Zhang; Zhen-Lu Zhang; Lin-Guang Li; Chun-Xiang You (Journal of Hazardous Materials, 2024)

Electrochemically mediated phosphorus and energy recovery from digested effluent - Ling-ling Lai; Si-zhuo Wan; Mahmood Qaisar; Yi-fan Yang; Ru Wang; Lin-jiang Yuan (Journal of Environmental Management, 2024)

Expression of polyphenol oxidase of Litopenaeus vannamei and its characterization - Qian Hong; Yu-Lei Chen; Duanquan Lin; Ru-Qing Yang; Kai-Yuan Cao; Ling-Jing Zhang; Yi-Ming Liu; Le-Chang Sun; Min-Jie Cao (Food Chemistry, 2024)

Study on low methoxyl pectin (LMP) with varied molecular structures cross-linked with calcium inducing differences in the gel properties - Chun-lin Wu; Jun-ru Qi; Jin-song Liao; Zi-wei Liu; Chun-ai He (Food Hydrocolloids, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Eco-friendly approach for enhancing the floatability of non-metallic components in waste printed circuit boards: Adding gutter oil during dry grinding - Chun-chen Nie; Si-qi Jiang; Xi-guang Li; Xiao-ru Wang; Zhi-hao Li; Xiang-nan Zhu; Xian-jun Lyu; Xiao-fang You; Lin Li (Waste Management, 2023)

Clarification of the phosphorus release mechanism for recovering phosphorus from biofilm sludge in alternating aerobic/anaerobic biofilm system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yang Pan; Lin Chen; Liang Zhu; Yi-Ping Li; Jing-Ru Li (Science of The Total Environment, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

A Potential Association of Zinc Deficiency and Tyrosine Kinase Inhibitor-Induced Hand-Foot Skin Reaction - Chun-Nan Yeh; Wen-Kuan Huang; Chun-Wei Lu; Chiao-Ping Chen; Sheng-Hsuan Lin; Yi-Ru Pan; Chiao-En Wu (Biological Trace Element Research, 2023)

Applying sheet iron to enhance the treatment efficiency of digested effluent with continuous flow and the corresponding mechanism - Cong Ding; Li-bin Chen; Li-ping Yu; Ru Wang; Lin-jiang Yuan; Lan Wang; Liang-wei Deng (Chemosphere, 2023)

Development of a duplex PCR for the simultaneous detection of EHP and IHHNV and analysis of the correlation between these two pathogens - Yang Gao; Cai-Yi Chen; Zheng Cao; Ru-Qing Yuan; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan; Fan Li (Journal of Invertebrate Pathology, 2023)

Excellent hydration properties and oil holding capacity of citrus fiber: Effects of component variation and microstructure - Chun-ai He; Jun-ru Qi; Jin-song Liao; Ya-ting Song; Chun-lin Wu (Food Hydrocolloids, 2023)

Prenatal and postnatal exposure to heavy metals in PM2.5 and autism spectrum disorder - Hao-Hsuan Lin; Chau-Ren Jung; Chuan-Yao Lin; Ya-Chu Chang; Chia-Yun Hsieh; Pei-Chuan Hsu; Bao-Ru Chuang; Bing-Fang Hwang (Environmental Research, 2023)

Paternal lipopolysaccharide exposure induced intrauterine growth restriction via the inactivation of placental MEST/PI3K/AKT pathway in mice - Pei-Ying Jiang; Shuai Lin; Jie-Ru Liu; Yan Liu; Li-Ming Zheng; Qiang Hong; Yi-Jun Fan; De-Xiang Xu; Yuan-Hua Chen (Archives of Toxicology, 2023)

Accumulation degree and risk assessment of metals in street dust from a developing city in Central Taiwan - Tser-Sheng Lin; Jun-Wei Wu; Thi-Dieu-Hien Vo; Van-Truc Nguyen; Yun-Ru Ju (Chemosphere, 2023)

Decreased levels of perfluoroalkyl substances in patients receiving hemodialysis treatment - Jih-Kai Huang; Yun-Shiuan Chuang; Ping-Hsun Wu; Chi-Jung Tai; Jye-Ru Lin; Mei-Chuan Kuo; Yi-Wen Chiu; Ping-Chi Hsu; Ming-Tsang Wu; Samira Salihovic; Yi-Ting Lin (Science of The Total Environment, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Reduction of pesticides and bacteria on Napa cabbage by ozone microbubble water - Hsiu-Ling Chen; Rachelle D. Arcega; Pei-Yu Liao; Chih-Yao Hou; Wen-Chun Liu; Yun-Ru Chen; Jong-Shinn Wu; Wan-Ru Wang; Chia-Min Lin (Postharvest Biology and Technology, 2023)

Characterizing basin-scale subsurface hydraulic heterogeneity with multiscale geological and hydrological measurements - Hong-Ru Lin; Jet-Chau Wen; Zaiyong Zhang; Yu-Li Wang (Journal of Hydrology, 2023)

Rethinking personal carbon trading (PCT) mechanism: A comprehensive review - Yun-En Tang; Ru Fan; Ang-Zu Cai; Le-Yi Wang; Rui-Min Lin; Xiang-Zhou Meng; Ling Chen; Ru Guo (Journal of Environmental Management, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

From arc accretion to within-plate extension: Geochronology and geochemistry of the Neoproterozoic magmatism on the northern margin of the Yangtze Block - Yu Huang; Xiao-Lei Wang; Jun-Yong Li; Ru-Cao Li; De-Hong Du; Chang-Hong Jiang; Lin-Sen Li; Ning Ding (Precambrian Research, 2023)

Phloroglucinol derivatives, coumarins and an alkaloid from the roots of Evodia lepta Merr. - Xiao-Ying Ding; Jun-Ru Wen; Wei-Yao Lin; Guo-Yong Huang; Qian Feng; Lixin Duan; Shi-Jie Zhang; Zhongqiu Liu; Rong-Rong Zhang; Ying Wang (Phytochemistry, 2023)

Metabolomic profiling of Panax ginseng in response to Fusarium solani infection - Guijia Zhao; Shuyang Xing; Yang Wang; Xu Yang; Ru Sun; Lin Feng; Jifeng Wang; Tianxia Sun; Wenhui Lian; Yu Zhao (Physiological and Molecular Plant Pathology, 2023)

CDN1163, a SERCA activator, causes intracellular Ca2+ leak, mitochondrial hyperpolarization and cell cycle arrest in mouse neuronal N2A cells - Yi-Ping Huang; Wen-Wei Huang; Kun-Feng Tsai; Lian-Ru Shiao; Zih-He Yang; Shao-Yun Tseng; Yu-Hsien Lin; Cing-Yu Chen; Paul Chan; Yuk-Man Leung (NeuroToxicology, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Enhancing fiber–matrix interface permeability resistance of natural fiber-reinforced, bio-cemented sand by CaCO 3 seed pretreatment - Liang Guo; Qichen Dai; Xingzhu Lin; Yuhong Jiang; Baoquan Wang; Xiaohua Pan; Yiqi Peng; Guoqiang Zhao; Yi Ru; Liye Zhou (Geomechanics for Energy and the Environment, 2023)

Effects of dietary starch and metformin levels on the growth performance, body composition, hepatic glycolipid metabolism, and liver histology of juvenile largemouth bass Micropterus salmoides - Qin-Qin Liu; Ru Xia; Xin Deng; Hui-Jun Yang; Li Luo; Shi-Mei Lin; Chuan-Jie Qin; Yong-Jun Chen (Aquaculture, 2023)

The sustainable treatment of chemical polishing wastewater under low-carbon economy: Pollutants removal, resource recovery and energy generation - Cong Ding; Meng-yu Liu; Si-zhuo Wan; Zhao-yang Cai; Lin-jiang Yuan; Ru Wang; Ping Zheng (Journal of Cleaner Production, 2023)

Variations of methane fluxes and methane microbial community composition with soil depth in the riparian buffer zone of a sponge city park - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Liangqian Fan; Wei Chen; Lin Cheng; et al. (Journal of Environmental Management, 2023)

First transcriptome profiling in gill and hepatopancrease tissues of Metapenaeus ensis in response to acute ammonia-N stress - Yun-Dong Li; Meng-Ru Si; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Li-Shi Yang; Jian-Hua Huang; Fa-Lin Zhou (Fish & Shellfish Immunology, 2023)

A marine lipopeptides-producing Bacillus amyloliquefaciens HY2-1 with a broad-spectrum antifungal and antibacterial activity and its fermentation kinetics study - Lin-ru Huang; Xiao-ning Ling; Shuai-ying Peng; Ming-hui Tan; Lu-qi Yan; Ying-yin Liang; Gang-hui Li; Kun-tai Li (World Journal of Microbiology and Biotechnology, 2023)

Three-dimensional flow and turbulence structure around Sea Cucumber Apostichopus japonicus - Yubing Lin; Haifei Liu; Zhiming Ru; Gangqin Tu; Zixin Wang (Ocean Engineering, 2023)

Isopropanol and styrene removal from aqueous solutions and simultaneous power generation using microbial fuel cells with encapsulated deoxygenated anodes - Shu-Hui Liu; Jun-Ru Ke; Hwai Chyuan Ong; Chi-Wen Lin (Journal of Water Process Engineering, 2023)

Ganglioside-focused Glycan Array Reveals Abnormal Anti-GD1b Auto-antibody in Plasma of Preclinical Huntington’s Disease - Tien-Wei Lin; Jung-Kai Chang; Yih-Ru Wu; Tsung-Hsien Sun; Yang-Yu Cheng; Chien-Tai Ren; Mei-Hung Pan; Jin-Lin Wu; Kuo-Hsuan Chang; Hwai-I Yang; Chiung-Mei Chen; Chung-Yi Wu; et al. (Molecular Neurobiology, 2023)

Applying expanded metal mesh for outdoor shades in outdoor thermal environments - Shing-Ru Yang; Shih-Tang Lan; Yi-Ting Wu; Tsuyoshi Honjo; Tzu-Ping Lin (International Journal of Biometeorology, 2023)

Exosomal MiR-381 from M2-polarized macrophages attenuates urethral fibroblasts activation through YAP/GLS1-regulated glutaminolysis - Ye-Hui Chen; Yi-Cheng Xu; Ting-Ting Lin; Hang Chen; Ru-Nan Dong; Feng-Ping Cai; Zhi-Bin Ke; Jia-Yin Chen; Yong Wei; Qing-Shui Zheng; Xue-Yi Xue; Ning Xu (Inflammation Research, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

PcCLCg is involved in the accumulation of Cl− in shoots for osmotic adjustment and salinity resistance in the Cl−-tolerant xerophyte Pugionium cornutum - Yan-Nong Cui; Zi-Ru Lin; Mei-Mei Cai; Rui-Wen Liu; Suo-Min Wang; Qing Ma (Plant and Soil, 2023)

Free and conjugated forms of metabolites are indispensable components of steroids: The first evidence from an estuarine food web - Shan Liu; Ru Xu; Yun-Feng Pan; Qian-Yi Huang; Nian-Nian Wu; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu (Water Research, 2023)

Melatonin reduces pink rib discoloration in wounded lettuce midribs - Catherine E. Belisle; Steven A. Sargent; Germán V. Sandoya; Jeffrey K. Brecht; Ru Dai; Bryce Askey; Zhentian Lei; Makou Lin; Jeongim Kim (Postharvest Biology and Technology, 2023)

Nanoplastics induce more severe multigenerational life-history trait changes and metabolic responses in marine rotifer Brachionus plicatilis: Comparison with microplastics - Xuan Li; Lin Lu; Shaoguo Ru; Junho Eom; Dong Wang; Samreen; Jun Wang (Journal of Hazardous Materials, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

A volatile producing Bacillus subtilis strain from the rhizosphere of Haloxylon ammodendron promotes plant root development - Ao-Lei He; Ling-Yu Zhao; Wei Ren; Hui-Ru Li; Paul W. Paré; Qi Zhao; Jin-Lin Zhang (Plant and Soil, 2023)

Characteristics and driving factors of abandoned cultivated land in the hilly regions of southern China: A case study in Longnan, Jiangxi Province - Ze-bin Chen; Yong-lin Chen; Chao-jun Li; Jian-ping Lin; Pei-ru Chen; Wei-wei Sun; Zhi-wei Wan (Journal of Mountain Science, 2023)

Extreme cooling of 12.5 °C triggered by Typhoon Fungwong (2008) - Zhe-Wen Zheng; Jia-Yi Lin; Ganesh Gopalakrishnan; Yi-Rui Chen; Doon-Jing Doong; Chung-Ru Ho; Quanan Zheng; Chau-Ron Wu; Chen-Fen Huang (Ocean Modelling, 2023)

A novel oxygen vacancies enriched Co Ni LDO catalyst activated peroxymonosulfate for the efficient degradation of tetracycline - Hao-Liang Jiang; Ming-Hui Li; Ling-Xi Zhao; Zhao-Xing Yan; Meng Xie; Jin-Ming Lin; Ru-Song Zhao (Journal of Water Process Engineering, 2023)

Magnetic ternary layered double hydroxides for efficient removal of 1-naphthalene acetic acid from waters: Adsorption behavior and mechanism - Ti-Bo Fang; Hua Xiao; Ling-Xi Zhao; Na Li; Ling-Yu Luan; Zhao-Xing Yan; Jin-Ming Lin; Ru-Song Zhao (Journal of Environmental Chemical Engineering, 2023)

Effect of nanoclay supported nanosilver on the growth inhibition of aquatic pathogens and immunomodulatory effect in Penaeus vannamei - Zhen-Hao Liao; Huai-Ting Huang; Yu-Ru Lin; Chi-Yun Hu; Yu-Hsuan Kai; Jiang-Jen Lin; Fan-Hua Nan (Fish & Shellfish Immunology, 2023)

Sleep disturbance in adults with untreated primary brain tumors: prevalence and impact on quality of life - Pei-Ching Lin; Pin-Yuan Chen; Kuo-Chen Wei; Jian-her Lin; Mei-Ru Lin; Huan-Chih Wang; Hsiao-Yean Chiu (Sleep and Biological Rhythms, 2023)

Plant identity shapes phyllosphere microbiome structure and abundance of genes involved in nutrient cycling - Jian Li; Ming-Kang Jin; Roy Neilson; Shi-Lin Hu; Yi-Jia Tang; Zhao Zhang; Fu-Yi Huang; Jing Zhang; Xiao-Ru Yang (Science of The Total Environment, 2023)

Sources, chemical components, and toxicological responses of size segregated urban air PM samples in high air pollution season in Guangzhou, China - Mo Yang; Hui-Xian Zeng; Xin-Feng Wang; Henri Hakkarainen; Ari Leskinen; Mika Komppula; Marjut Roponen; Qi-Zhen Wu; Shu-Li Xu; Li-Zi Lin; Ru-Qing Liu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Direct emissions of particulate glyoxal and methylglyoxal from biomass burning and coal combustion - Ting Wang; Ru-Jin Huang; Lu Yang; Wenting Dai; Haiyan Ni; Yuquan Gong; Jie Guo; Haobin Zhong; Chunshui Lin; Wei Xu (Science of The Total Environment, 2023)

Halogen microregulation in metal-organic frameworks for enhanced adsorption performance of ReO4-/TcO4- - Qing-Hua Hu; You-Gan Wang; Xin Gao; Yu-Zhen Shi; Sen Lin; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Room-temperature synthesis of nitrogen-rich conjugated microporous polymers for solid-phase extraction of trace synthetic musks - Ye-Fei Fan; Hai-Long Jiang; Xiang-Feng Chen; Na Li; Xiao-Li Wang; Jin-Ming Lin; Ru-Song Zhao (Food Chemistry, 2023)

Carnosic acid attenuated cytochrome c release through the mitochondrial structural protein Mic60 by PINK1 in SH-SY5Y cells - Chia-Yuan Lin; Yi-Chen Huang; Chi-Rei Wu; Han-Ting Wu; Ru-Huei Fu; Chia-Wen Tsai (Food and Chemical Toxicology, 2023)

Chronic exposure to di(2-ethylhexyl) phthalate (DEHP) weakens innate immunity and leads to immunosenescence in C. elegans - Pei-Ling Yen; Cai-Ru Yang; Mei-Lun Huang; Ting-An Lin; Vivian Hsiu-Chuan Liao (Environmental Toxicology and Pharmacology, 2023)

Engelheptanoxides behave as liver X receptor α agonists - Yu-Hsuan Liang; Yu-Han Luo; Ih-Sheng Chen; Hsiang-Ru Lin (Medicinal Chemistry Research, 2023)

Dynamic changes in cell wall-degrading enzymes and physio-biochemistry of ginseng in response to fusarium oxysporum infection - Lin Feng; Guijia Zhao; Ru Sun; Jifeng Wang; Tianxia Sun; Shuyang Xing; Wenhui Lian; Yu Zhao (European Journal of Plant Pathology, 2023)

Parameter optimization of coal face blasting for coal and gas outburst control - Wei Yang; Wenyuan Wang; Ru Jia; Gabriel Walton; Sankhaneel Sinha; Qinghe Chen; Baiquan Lin; Xiangdong Jiao (Bulletin of Engineering Geology and the Environment, 2023)

Condition optimization of iron-air fuel cell to treat phosphate-containing wastewater regarding sustainable development - Ling-ling Lai; Chao Liu; Meng-yu Liu; Si-zhuo Wan; Zhi-guo Zhao; Ru Wang; Lin-jiang Yuan (Chemosphere, 2023)

COSEν: A collective oscillation simulation engine for neutrinos - Manu George; Chun-Yu Lin; Meng-Ru Wu; Tony G. Liu; Zewei Xiong (Computer Physics Communications, 2023)

Molecular characterization of humic-like substances (HULIS) in atmospheric particles (PM2.5) in offshore Eastern China Sea (OECS) using solid-phase extraction coupled with ESI FT-ICR MS - Hao Sun; Zilan Wu; Xinyuan Kang; Chao Zhu; Limin Yu; Ru Li; Zhongsheng Lin; Jianmin Chen (Atmospheric Environment, 2023)

Plastome evolution and phylogenomics of Impatiens (Balsaminaceae) - He Qiu; Zhi-Hui Zhang; Mei-Zhen Wang; Xin-Jie Jin; Jie-Dong Lin; Hans Peter Comes; Jing-Xuan Chen; Rui-Ning Cui; Ru-Qing Duan; Pan Li (Planta, 2023)

Temporal dynamics of soil bacterial network regulate soil resistomes - Qian Xiang; Dong Zhu; Min Qiao; Xiao‐Ru Yang; Gang Li; Qing‐Lin Chen; Yong‐Guan Zhu (Environmental Microbiology, 2023)
Soil bacteria are diverse and form complicated ecological networks through various microbial interactions, which play important roles in soil multi‐functionality. However, the seasonal effects on the bacterial network, especially the relationship between bacterial network topological features and soil resistomes remains underexplored, which impedes our ability to unveil the mechanisms of the temporal‐dynamics of antibiotic resistance genes (ARGs). Here, a field investigation was conducted across four seasons at the watershed scale. We observed significant seasonal variation in bacterial networks, with lower complexity and stability in autumn, and a wider bacterial community niche in summer. Similar to bacterial communities, the co‐occurrence networks among ARGs also shift with seasonal change, particularly with respect to the topological features of the node degree, which on average was higher in summer than in the other seasons. Furthermore, the nodes with higher betweenness, stress, degree, and closeness centrality in the bacterial network showed strong relationships with the 10 major classes of ARGs. These findings highlighted the changes in the topological properties of bacterial networks that could further alter antibiotic resistance in soil. Together, our results reveal the temporal dynamics of bacterial ecological networks at the watershed scale, and provide new insights into antibiotic resistance management under environmental changes.

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Association between long-term ambient ozone exposure and attention-deficit/hyperactivity disorder symptoms among Chinese children - Peien Zhou; Wangjian Zhang; Yu-Jie Xu; Ru-Qing Liu; Zhengmin Qian; Stephen Edward McMillin; Elizabeth Bingheim; Li-Zi Lin; Xiao-Wen Zeng; Bo-Yi Yang; Li-Wen Hu; Wen Chen; et al. (Environmental Research, 2023)

Realizing the bifunctional electrocatalysis via local charge rearrangement of α-CrOOH-modulated Co@CoMoOx for overall water splitting - Suh-Ciuan Lim; Chao-Lung Chiang; Chun-Kuo Peng; Wen-Bin Wu; Yu-Chang Lin; Yu-Ru Lin; Chi-Liang Chen; Yan-Gu Lin (Chemical Engineering Journal, 2023)

Clustered regularly interspaced short palindromic repeats (CRISPR) technology and genetic engineering strategies for microalgae towards carbon neutrality: A critical review - Tse-Min Lee; Jia-Yi Lin; Tsung-Han Tsai; Ru-Yin Yang; I-Son Ng (Bioresource Technology, 2023)

Application of hybrid machine learning model for flood hazard zoning assessments - Jhih-Huang Wang; Gwo-Fong Lin; Yun-Ru Huang; I-Hang Huang; Chieh-Lin Chen (Stochastic Environmental Research and Risk Assessment, 2023)

Three-dimensional hydroxylated covalent organic frameworks for solid phase extraction of glucocorticoids in environmental water samples - Chuqing Liu; Guiju Xu; Baoyu Li; Xiaoli Wang; Jin-Ming Lin; Ru-Song Zhao (Analytica Chimica Acta, 2023)

Nitrogen enrichment alters multiple dimensions of grassland functional stability via changing compositional stability - Qianna Xu; Xian Yang; Jian Song; Jingyi Ru; Jianyang Xia; Shaopeng Wang; Shiqiang Wan; Lin Jiang (Ecology Letters, 2022)
Anthropogenic nutrient enrichment is known to alter the composition and functioning of plant communities. However, how nutrient enrichment influences multiple dimensions of community‐ and ecosystem‐level stability remains poorly understood. Using data from a nitrogen (N) and phosphorus (P) addition experiment in a temperate semi‐arid grassland that experienced a natural drought, we show that N enrichment, not P enrichment, decreased grassland functional and compositional temporal stability, resistance and recovery but increased functional and compositional resilience. Compositional stability and species asynchrony, rather than species diversity, were identified as key determinants of all dimensions of grassland functional stability, except for recovery. Whereas grassland functional recovery was decoupled from compositional recovery, N enrichment altered other dimensions of functional stability primarily through changing their corresponding compositional stability dimensions. Our findings highlight the need to examine ecological stability at the community level for a more mechanistic understanding of ecosystem dynamics in the face of environmental change.

Complete genome sequence of Aconitum amalgavirus 1, a distinct member of the genus Amalgavirus - Jie Yang; Ping-Xiu Lan; Jin-Ming Li; Xiao-Jiao Chen; Guan-Lin Tan; Tai-Yun Wei; Ru-Hui Li; Fan Li (Archives of Virology, 2022)

The Key Role of Magnetic Resonance Imaging in the Detection of Neurodegenerative Diseases-Associated Biomarkers: A Review - Ke-Ru Li; An-Guo Wu; Yong Tang; Xiao-Peng He; Chong-Lin Yu; Jian-Ming Wu; Guang-Qiang Hu; Lu Yu (Molecular Neurobiology, 2022)

Strength and deformation behavior of columnar jointed rock masses under different confining pressures - Zhi-nan Lin; Hai-feng Long; Wei-ya Xu; Ru-bin Wang; Shi-hong Feng (Arabian Journal of Geosciences, 2022)

Vibrio salinus sp. nov., a marine nitrogen-fixing bacterium isolated from the lagoon sediment of an islet inside an atoll in the western Pacific Ocean - Wei-Sheng Huang; Li-Ting Wang; Jwo-Sheng Chen; Yen-Ting Chen; Sean Ting-Shyang Wei; Yin-Ru Chiang; Pei-Ling Wang; Tzong-Huei Lee; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2022)

Age, Growth and Population Structure Analyses of the Purpleback Flying Squid Sthenoteuthis oualaniensis in the Northwest Indian Ocean by Beak Microstructure - Hua-Jie Lu; Yu-Zhe Ou; Jing-Ru He; Mao-Lin Zhao; Zi-Yue Chen; Xin-Jun Chen (Journal of Marine Science and Engineering, 2022)
To explore the feasibility of using beak microstructure information to estimate the age of Sthenoteuthis oualaniensis, the microstructures of the upper beaks of individual squid were applied in this work to analyze the ages and growth patterns of squid caught from February–May 2019 and from October–December 2020 in the northwest Indian Ocean. The results indicated that the squid samples in the two years were no older than 9 months, and the samples in 2019 were autumn population and 2020 were spring population. The linear growth model of the autumn population (2019) was the best model for describing the relationship between age and ML, while the power model of the spring population (2020) was the best for describing the relationship between age and ML. The maximum instantaneous growth rate (IGR) and absolute daily growth rate (AGR) values of the spring population were 0.24%/d and 1.09 mm/d, respectively, occurring in squid between 200 and 220 days of age. The maximum IGR and AGR values of the autumn population were 0.69%/d and 1.73 mm/d, respectively, occurring in squid between 200 and 240 days of age. The period from 141–260 days (5–8 months) was considered to correspond to the subadult stage in the whole life history of S. oualaniensis in the Northwest Indian Ocean. The beak microstructure information can be effectively applied to estimate the age of S. oualaniensis individuals.

Stachybotranes A–D, phenylspirodrimanes from the wetland fungus Stachybotrys chartarum with cytotoxic activities - Yan-Ru Bao; Han-Lin Feng; Xin-Sheng Yao (Natural Product Research, 2022)

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Dataset-based assessment of heavy metal contamination in freshwater fishes and their health risks - Xiao-Bo Liu; Congtian Lin; Yang-Yu Wu; Hai-Ning Huang; Li-Ting Zhu; Ru Jiang; Qiansheng Huang (Environmental Science and Pollution Research, 2022)

High Levels of 25-OH-Vitamin D and Copper in Pregnant Women with Abnormal Glucose Challenge Test - Chien-Hua Chiang; Wan-Ju Kung; Chien-Hung Lee; Yeong-Hwa Zen; Cheng-Fa Lee; Hui-Ru Yang; Ching-Chiang Lin; Yeou-Lih Huang (Biological Trace Element Research, 2022)

Phenomenon of the sediment deposition in a hydraulic jump region of open channels - Wei-lin Xu; Guo-guang Wang; Shi-hao Fu; Wang-ru Wei (Journal of Mountain Science, 2022)

Detection of bloom-forming dinoflagellates Karenia mikimotoi and Prorocentrum donghaiense using qPCR assays - Xiao-Kun Hu; Zhuo-Ru Lin; Qing-Chun Zhang; Fan-Zhou Kong; Jing-Yi Cen; Yu-Lan Zeng; Ren-Cheng Yu (Journal of Applied Phycology, 2022)

Clinical efficacy of melatonin as adjunctive therapy to non-surgical treatment of periodontitis: a systematic review and meta-analysis - Ru-Yue Liu; Lin Li; Zhong-Ti Zhang; Ting Wu; Shuang Lin; Xu-Tong Zhang (Inflammopharmacology, 2022)

Analyzing the mechanism of nitrous oxide production in aerobic phase of anoxic/aerobic sequential batch reactor from the perspective of key enzymes - Rui Yang; Lin-jiang Yuan; Ru Wang; Zhi-xian He; Lin Lei; Yan-chen Ma (Environmental Science and Pollution Research, 2022)

Exploiting Sentinel-1 data and machine learning–based random forest for collectively mapping rice fields in Taiwan - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Youg-Sin Cheng; Piero Toscano; Chein-Hui Syu; Horng-Yuh Guo; Shu-Ling Chen; Tsang-Sen Liu; Yi-Ting Zhang; Huan-Sheng Lin; Shih-Hsiang Chen; et al. (Applied Geomatics, 2022)

Natural Feed Supplements Improve Growth, Non-Specific Immune Responses and Resistance against Vibrio alginolyticus in Lates calcarifer - Zhen-Hao Liao; Huai-Ting Huang; Yu-Ru Lin; Bo-Ying Chen; Yi-Fan Lee; Yuan-Heng Lin; Chieh-Yuan Chuang; Fan-Hua Nan (Journal of Marine Science and Engineering, 2022)
This study aimed to investigate the effects of dietary natural feed supplement on the growth performance, non-specific responses, and disease resistance in Lates calcarifer. Three commercial products (A, B, and C) containing a basal probiotic mixture were tested. Product A contained a basal mixture of Paenibacillus sp., Bacillus subtilis, Bacillus amyloliquefaciens, and Lactobacillus rhamnosus (107 cfu/g for each probiotic); product B contained additional Lactobacillus plantarum (1010 cfu/g); and product C contained additional soybean peptides (500 g/kg) and garlic powder (1 g/kg). Each product was supplemented into subject diets at dosages of 1 or 2 g/kg (designated as the A1, A2, B1, B2, C1, and C2 groups, respectively). Following an eight-week trial, growth parameters (specific growth rate and feed conversion ratio), non-specific immune responses (O2− production, phagocytic rate, and phagocytic index), and the results of a challenge test against Vibrio alginolyticus were evaluated. The results show that all probiotic supplement groups exhibited an improvement in growth performance compared to the control group (non-probiotic diet). In terms of non-specific immunity parameters, a significant improvement in O2− production was found in the C2 group, whereas significant improvements in phagocytic activity were found in all the B and C groups. The C2 group displayed optimal O2− production, phagocytic rate, and phagocytic index results. For the challenge test, the C groups showed higher Vibrio resistance than the other experimental groups and the control group. These results suggest that product C, given at dosages of 2 g/kg, may serve as a growth-promoting and immunostimulatory additive for the cultivation of Asian seabass.

Genomic characterization of a new enamovirus infecting common bean - Ruo-bin Lu; Ping-xiu Lan; Ru-jing Kang; Guan-lin Tan; Xiao-jiao Chen; Ruhui Li; Fan Li (Archives of Virology, 2022)

Identification and antimicrobial properties of a new alkaloid produced by marine-derived Verrucosispora sp. FIM06-0036 - Ming-Hong Chen; Yun-Yang Lian; Dong-Sheng Fang; Li Chen; Jia Jia; Wen-Long Zhang; Ru Lin; Yang Xie; Hong-Kai Bi; Hong Jiang (Natural Product Research, 2021)

Anti-miR33 therapy improved hepatopancreatic lipid and immune metabolism disorders in grass carp, Ctenopharyngodon idella - Rong-Hua Lu; Meng-Jun Lin; Feng Yang; Shen-zong Jia; Yu-Ru Zhang; Chao-Bin Qin; Xiao-Lin Meng; Guo-Xing Nie (Fish Physiology and Biochemistry, 2021)

Contamination, source attribution, and potential health risks of heavy metals in street dust of a metropolitan area in Southern Vietnam - Nguyen Duy Dat; Van-Truc Nguyen; Thi-Dieu-Hien Vo; Xuan-Thanh Bui; Manh-Ha Bui; Ly Sy Phu Nguyen; Xuan-Cuong Nguyen; Anh Thi-Kim Tran; Thi-Tinh-Au Nguyen; Yun-Ru Ju; Thi-Minh-Trang Huynh; Duy-Hieu Nguyen; et al. (Environmental Science and Pollution Research, 2021)

Taxonomic description of Pseudomonas rhizovicinus sp. nov., isolated from the rhizosphere of a desert shrub Haloxylon ammodendron - Ao-Lei He; Hui-Ru Li; Hui-Ping Li; Jing-Yi Gou; Jia Chen; Qi Zhao; Jin-Lin Zhang (Antonie van Leeuwenhoek, 2021)

Prediction of Metabolic Disorders Using NMR-Based Metabolomics: The Shanghai Changfeng Study - Qi Wu; Qing-xia Huang; Hai-luan Zeng; Shuai Ma; Huan-dong Lin; Ming-feng Xia; Hui-ru Tang; Xin Gao (Phenomics, 2021)

Present in-situ stress distribution characteristics of strike-slip in SH Oilfield, Tarim Basin - Teng Zhao; Wenge Hu; Rui Zhao; Min Yang; Qiang Wang; Huixi Lin; Zhixing Ru; Dian Bao; Fei Cao (Arabian Journal of Geosciences, 2021)

Cysteiniphilum marinum sp. nov., isolated from coastal seawater - Hai-Min Luo; Jun-Hui Feng; Liang-Hui Li; Meng-Meng Li; Ru-Qin Liu; Fu Chen; Ying Lin; Wen-Jun Li; Ping-Hua Qu; Min Xiao (Antonie van Leeuwenhoek, 2021)

Vibrio nitrifigilis sp. nov., a marine nitrogen-fixing bacterium isolated from the lagoon sediment of an islet inside an atoll - Wei-Sheng Huang; Li-Ting Wang; Jwo-Sheng Chen; Yen-Ting Chen; Sean Ting-Shyang Wei; Yin-Ru Chiang; Pei-Ling Wang; Tzong-Huei Lee; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2021)

Luteolin alleviates ulcerative colitis through SHP-1/STAT3 pathway - Bo-Lin Li; Dan-Yang Zhao; Peng-Li Du; Xiao-Tian Wang; Qian Yang; Yan-Ru Cai (Inflammation Research, 2021)

Prediction of oral hepatotoxic dose of natural products derived from traditional Chinese medicines based on SVM classifier and PBPK modeling - Size Li; Yiqun Yu; Xiaolan Bian; Li Yao; Min Li; Yan-Ru Lou; Jing Yuan; Hai-shu Lin; Lucy Liu; Bing Han; Xiaoqiang Xiang (Archives of Toxicology, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Selective Ferroptosis Inhibitor Liproxstatin-1 Attenuates Neurological Deficits and Neuroinflammation After Subarachnoid Hemorrhage - Yang Cao; Yin Li; Chao He; Feng Yan; Jian-Ru Li; Hang-Zhe Xu; Jian-Feng Zhuang; Hang Zhou; Yu-Cong Peng; Xiong-Jie Fu; Xiao-Yang Lu; Yuan Yao; et al. (Neuroscience Bulletin, 2021)

A study on the reservoir controlling characteristics and mechanism of the strike slip faults in the northern slope of Tazhong uplift, Tarim Basin, China - Zhongpei Zhang; Yuan Kang; Huixi Lin; Jun Han; Rui Zhao; Xiuxiang Zhu; Zhixing Ru; Chongyang Xiao (Arabian Journal of Geosciences, 2021)

Re-use of wasted sludge to treat industrial pollutants - Ru Wang; Li-ping Yu; Bibi Saima Zeb; Lin-jie Yuan; Meng-yu Liu; Lin-jiang Yuan (Water, Air, & Soil Pollution, 2021)

Biomimetic Au nanodot synthesis using Escherichia coli secretion and interaction with α-ketoglutaric acid - Xiaoxiao Xie; Xiaoli Yang; Yi Chang; Xiangli Ru; Xiaoming Ma; Lin Yang (Science China Life Sciences, 2021)

Effects of Grazing, Wind Erosion, and Dust Deposition on Plant Community Composition and Structure in a Temperate Steppe - Mengmei Zheng; Jian Song; Jingyi Ru; Zhenxing Zhou; Mingxing Zhong; Lin Jiang; Dafeng Hui; Shiqiang Wan (Ecosystems, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

FW0622, a new siderophore isolated from marine Verrucosispora sp. by genomic mining - Wei Zhao; Fei Peng; Chuan-xi Wang; Yang Xie; Ru Lin; Zhi-kai Fang; Fei Sun; Yun-yang Lian; Hong Jiang (Natural Product Research, 2020)

Machine learning approaches for rice crop yield predictions using time-series satellite data in Taiwan - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Horng-Yuh Guo; Youg-Sing Cheng; Shu-Ling Chen; Huan-Sheng Lin; Shih-Hsiang Chen (International Journal of Remote Sensing, 2020)

Emerging relationship between RNA helicases and autophagy - Miao-miao Zhao; Ru-sha Wang; Yan-lin Zhou; Zheng-gang Yang (Journal of Zhejiang University-SCIENCE B, 2020)

Grape seed proanthocyanidin extract ameliorates hepatic lipid accumulation and inflammation in grass carp (Ctenopharyngodon idella) - Rong-Hua Lu; Chao-Bin Qin; Feng Yang; Wen-Ya Zhang; Yu-Ru Zhang; Guo-Kun Yang; Li-Ping Yang; Xiao-Lin Meng; Xiao Yan; Guo-Xing Nie (Fish Physiology and Biochemistry, 2020)

Multiplex RT–PCR Assay for the Simultaneous Detection and Identification of Five Sugarcane Viruses - Xiao-Yan Feng; Wen-Zhi Wang; Lin-Bo Shen; Jun-Gang Wang; Guo-Ru Xiong; Cui-Lian Feng; Ting-Ting Zhao; Shu-Zhen Zhang (Sugar Tech, 2020)

Impaired Parahippocampal Gyrus–Orbitofrontal Cortex Circuit Associated with Visuospatial Memory Deficit as a Potential Biomarker and Interventional Approach for Alzheimer Disease - Lin Zhu; Zan Wang; Zhanhong Du; Xinyang Qi; Hao Shu; Duan Liu; Fan Su; Qing Ye; Xuemei Liu; Zheng Zhou; Yongqiang Tang; Ru Song; et al. (Neuroscience Bulletin, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Enhanced Antitumor Efficacy of Curcumin-Loaded PLGA Nanoparticles Coated with Unique Fungal Hydrophobin - Lu Sun; Hui Xu; Jing-hua Xu; Shao-ning Wang; Jun-wei Wang; Hong-feng Zhang; Wei-ru Jia; Lin-sen Li (AAPS PharmSciTech, 2020)

Influence of Aphis gossypii feeding on defense strategy of native and introduced populations of Ageratina adenophora - Ying Lin; Shu-Qi He; Zhi-Hui Lu; Yu-Lin Gao; Yan-Ru Duan; Zheng-Yue Li; Bin Chen; Fu-Rong Gui (Arthropod-Plant Interactions, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Endometrial autophagy is essential for embryo implantation during early pregnancy - Yan Su; Juan-Juan Zhang; Jun-Lin He; Xue-Qing Liu; Xue-Mei Chen; Yu-Bin Ding; Chao Tong; Chuan Peng; Yan-Qing Geng; Ying-Xiong Wang; Ru-Fei Gao (Journal of Molecular Medicine, 2020)

Effects of small nucleolar RNA SNORD44 on the proliferation, apoptosis and invasion of glioma cells - Xian-Ru Xia; Wen-Cui Li; Zong-Tao Yu; Jie Li; Chun-Yan Peng; Li Jin; Guo-Lin Yuan (Histochemistry and Cell Biology, 2020)

Isolation, purification and identification of two new alkaloids metabolites from marine-derived Verrucosispora sp. FIM06025 - Ming-Hong Chen; Wen-Long Zhang; Li Chen; Ru Lin; Yang Xie; Dong-Sheng Fang; Yun-Yang Lian; Hong Jiang (Natural Product Research, 2019)

The complete chloroplast genome of Taiwania cryptomerioides (Cupressales: Cupressaceae), an endangered relict conifer species endemic to East Asia - Ling-Li Wang; Yong-Liang Shi; Qi-Lin Zhang; Yan-Ru Guo; Hong-Mei Teng (Conservation Genetics Resources, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

The Neuroprotective Effect of L-Stepholidine on Methamphetamine-Induced Memory Deficits in Mice - Mei Zhou; Xiaokang Gong; Qin Ru; Qi Xiong; Lin Chen; Yuanren Si; Huaqiao Xiao; Chaoying Li (Neurotoxicity Research, 2019)

Antagonism of Ca2+-sensing receptors by NPS 2143 is transiently masked by p38 activation in mouse brain bEND.3 endothelial cells - Cing-Yu Chen; Mann-Jen Hour; Wen-Chuan Lin; Kar-Lok Wong; Lian-Ru Shiao; Ka-Shun Cheng; Paul Chan; Yuk-Man Leung (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

The potential of a modified physiologically equivalent temperature (mPET) based on local thermal comfort perception in hot and humid regions - Tzu-Ping Lin; Shing-Ru Yang; Yung-Chang Chen; Andreas Matzarakis (Theoretical and Applied Climatology, 2019)

Comparative proteomic analysis of Nostoc flagelliforme reveals the difference in adaptive mechanism in response to different ultraviolet-B radiation treatments - Shi-gang Shen; Rong-jun Guo; Rong-rong Yan; Yi-kai Wu; Dong-xue Zhao; Ya-hui Lin; He-xin Lv; Shi-ru Jia; Pei-pei Han (Molecular Biology Reports, 2018)

Cyproheptadine Regulates Pyramidal Neuron Excitability in Mouse Medial Prefrontal Cortex - Yan-Lin He; Kai Wang; Qian-Ru Zhao; Yan-Ai Mei (Neuroscience Bulletin, 2018)

Structure elucidation and antitumour activity of a new macrolactam produced by marine-derived actinomycete Micromonospora sp. FIM05328 - Yi-Lei Nie; Yun-Dan Wu; Chuan-Xi Wang; Ru Lin; Yang Xie; Dong-Sheng Fang; Hong Jiang; Yun-Yang Lian (Natural Product Research, 2018)

Whole-genome sequence and genome annotation of Xanthomonas citri pv. mangiferaeindicae, causal agent of bacterial black spot on Mangifera indica - Feng Liu; Xiong-chang Ou; Ru-lin Zhan (Archives of Microbiology, 2018)

Annual dynamics of impervious surfaces at city level of Pearl River Delta metropolitan - Ru Xu; Hongsheng Zhang; Hui Lin (International Journal of Remote Sensing, 2018)

Anti-amyloidgenic and neurotrophic effects of tetrahydroxystilbene glucoside on a chronic mitochondrial dysfunction rat model induced by sodium azide - Ru-yi Zhang; Lan Zhang; Li Zhang; Yu-lan Wang; Lin Li (Journal of Natural Medicines, 2018)

Genetic analysis of three porcine bocaparvoviruses and identification of a natural recombinant breakpoint in NS1 - Yu Zhou; Jia Xu; Shi-Kang Zhu; Qing-Feng Meng; Zhi-Xiong Lin; Ru Chen; Ai-Dong Qian (Archives of Virology, 2018)

Modulation of ARTS and XIAP by Parkin Is Associated with Carnosic Acid Protects SH-SY5Y Cells against 6-Hydroxydopamine-Induced Apoptosis - Ru-Huei Fu; Li-Chun Huang; Chia-Yuan Lin; Chia-Wen Tsai (Molecular Neurobiology, 2018)

Echinacoside, a phenylethanoid glycoside from Cistanche deserticola, extends lifespan of Caenorhabditis elegans and protects from Aβ-induced toxicity - Wei Chen; Hong-Ru Lin; Cong-Min Wei; Xiao-Hua Luo; Meng-Lu Sun; Zhen-Zhou Yang; Xin-Yan Chen; Hong-Bing Wang (Biogerontology, 2018)

Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Groundwater origins and recharge in a well field near Chien-Shih, Shinchu, Taiwan - Pei-Ying Lin; Louis Loung-Yie Tsai; Chung-Ho Wang; Kuei-Wen Chang; Yu-Yen Sheng; I-Tzu Chu; Wang-Ru Lee (Sustainable Water Resources Management, 2017)

Activation of liver X receptor α protects amyloid β1–40 induced inflammatory and senescent responses in human retinal pigment epithelial cells - Bingling Dai; Chunyan Lei; Ru Lin; Lifei Tao; Yue Bin; Hui Peng; Bo Lei (Inflammation Research, 2017)

Propofol attenuates H2O2-induced oxidative stress and apoptosis via the mitochondria- and ER-medicated pathways in neonatal rat cardiomyocytes - Xue-Ru Liu; Lu Cao; Tao Li; Lin-Lin Chen; Yi-Yan Yu; Wen-Jun Huang; Li Liu; Xiao-Qiu Tan (Apoptosis, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Transplantation of collagen scaffold with autologous bone marrow mononuclear cells promotes functional endometrium reconstruction via downregulating ΔNp63 expression in Asherman’s syndrome - Guangfeng Zhao; Yun Cao; Xianghong Zhu; Xiaoqiu Tang; Lijun Ding; Haixiang Sun; Juan Li; Xinan Li; Chenyan Dai; Tong Ru; Hui Zhu; Jingjie Lu; et al. (Science China Life Sciences, 2017)

Impacts of climate variability and changes on domestic water use in the Yellow River Basin of China - Xiao-jun Wang; Jian-yun Zhang; Shahid Shamsuddin; Ru-lin Oyang; Tie-sheng Guan; Jian-guo Xue; Xu Zhang (Mitigation and Adaptation Strategies for Global Change, 2017)

Overexpression of the ascorbate peroxidase gene from eggplant and sponge gourd enhances flood tolerance in transgenic Arabidopsis - Chih-Ming Chiang; Chiu-Chen Chen; Shi-Peng Chen; Kuan-Hung Lin; Li-Ru Chen; Yu-Huei Su; His-Cheng Yen (Journal of Plant Research, 2017)

An integrated earthquake early warning system and its performance at schools in Taiwan - Bing-Ru Wu; Nai-Chi Hsiao; Pei-Yang Lin; Ting-Yu Hsu; Chiou-Yun Chen; Shieh-Kung Huang; Hung-Wei Chiang (Journal of Seismology, 2017)

Improved salt tolerance of medicinal plant Codonopsis pilosula by Bacillus amyloliquefaciens GB03 - Qing-Qing Han; Yong-Na Wu; Hui-Juan Gao; Rui Xu; Paul W. Paré; Huazhong Shi; Qi Zhao; Hui-Ru Li; Sardar Ali Khan; Yin-Quan Wang; Suo-Min Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2017)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

Induced growth promotion and higher salt tolerance in the halophyte grass Puccinellia tenuiflora by beneficial rhizobacteria - Shu-Qi Niu; Hui-Ru Li; Paul W. Paré; Mina Aziz; Suo-Min Wang; Huazhong Shi; Jing Li; Qing-Qing Han; Shi-Qian Guo; Jian Li; Qiang Guo; Qing Ma; et al. (Plant and Soil, 2016)

A genome-wide analysis of the ASYMMETRIC LEAVES2/LATERAL ORGAN BOUNDARIES (AS2/LOB) gene family in barley (Hordeum vulgare L.) - Bao-jian Guo; Jun Wang; Shen Lin; Zheng Tian; Kai Zhou; Hai-ye Luan; Chao Lyu; Xin-zhong Zhang; Ru-gen Xu (Journal of Zhejiang University-SCIENCE B, 2016)

Dietary lipid concentrations influence growth, liver oxidative stress, and serum metabolites of juvenile hybrid snakehead (Channa argus × Channa maculata) - Peng-Fei Zhao; Fa-Jian Li; Xiao-Ru Chen; Yong-Jun Chen; Shi-Mei Lin; Lu Zhang; Yun Li (Aquaculture International, 2016)

Mild Hypothermia Combined with Hydrogen Sulfide Treatment During Resuscitation Reduces Hippocampal Neuron Apoptosis Via NR2A, NR2B, and PI3K-Akt Signaling in a Rat Model of Cerebral Ischemia-Reperfusion Injury - Hai-Bin Dai; Miao-Miao Xu; Jia Lv; Xiang-Jun Ji; Si-Hai Zhu; Ru-Meng Ma; Xiao-Lei Miao; Man-Lin Duan (Molecular Neurobiology, 2016)

G2 rotavirus within an emergent VP7 evolutionary lineage circulating in children with acute diarrhea in Guangxi Province of China, 2014 - Hui Jin Dong; Yuan Qian; You Zhang; Lin Qing Zhao; Ru Nan Zhu; Yi Nong; Zhao Jun Mo; Rong Cheng Li (Archives of Virology, 2016)

Influence of Soluplus on Solid-State Properties and Physical Stability of Indomethacin-Saccharin Co-crystal Formation Prepared by Air-Drying Process - Shan-Yang Lin; Hong-Liang Lin; Ying-Ting Chi; Ru-Ying Hung; Yu-Ting Huang; Wei-Hsien Hsieh; Chi-Yu Kao (Journal of Pharmaceutical Innovation, 2016)

Study on effects of endophytes on growth and production of Z-Ligustilide and ferulic acid in Angelica sinensis - Xin-Guo Zhang; Xiao-Ru Li; Qiang-Lin Wang; Wen-Na Wang; Xiao-Qian Chen (Brazilian Journal of Botany, 2016)

Genomic variability and molecular evolution of Asian isolates of sugarcane streak mosaic virus - Shan-Shan Liang; Olufemi J. Alabi; Mona B. Damaj; Wei-Lin Fu; Sheng-Ren Sun; Hua-Ying Fu; Ru-Kai Chen; T. Erik Mirkov; San-Ji Gao (Archives of Virology, 2016)

Cytomolecular characterization and origin of de novo formed maize B chromosome variants - Ya-Ming Cheng; Ying-Ru Feng; Yao-Pin Lin; Shu-Fen Peng (Chromosome Research, 2016)

Differential expression of ATP-gated P2X receptors in DRG between chronic neuropathic pain and visceralgia rat models - Lin Chen; Yu-wei Liu; Kai Yue; Qin Ru; Qi Xiong; Bao-miao Ma; Xiang Tian; Chao-ying Li (Purinergic Signalling, 2016)

Customized rating assessment of climate suitability (CRACS): climate satisfaction evaluation based on subjective perception - Tzu-Ping Lin; Shing-Ru Yang; Andreas Matzarakis (International Journal of Biometeorology, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Invasive fungal infection in allogeneic hematopoietic stem cell transplant recipients: single center experiences of 12 years - Ji-min Shi; Xu-ying Pei; Yi Luo; Ya-min Tan; Ru-xiu Tie; Jing-song He; Wei-yan Zheng; Jie Zhang; Zhen Cai; Mao-fang Lin; He Huang (Journal of Zhejiang University-SCIENCE B, 2015)

Association between vitamin D receptor gene polymorphism (TaqI) and obesity in Chinese population - HUI-RU FAN; LI-QUN LIN; HAO MA; YING LI; CHANG-HAO SUN (Journal of Genetics, 2015)

Environmental stochasticity promotes copper bioaccumulation and bioenergetic response in tilapia - Wei-Yu Chen; Yun-Ru Ju; Chia-Jung Lin; Jeng-Wei Tsai; Szu-Cheih Chen; Chung-Min Liao (Stochastic Environmental Research and Risk Assessment, 2015)

Effect of microRNA-203 on tumor growth in human hypopharyngeal squamous cell carcinoma - Ru Wang; Jugao Fang; Hongzhi Ma; Lin Feng; Meng Lian; Fan Yang; Haizhou Wang; Qi Wang; Xiaohong Chen (Molecular and Cellular Biochemistry, 2015)

Two homoisoflavonoids act as peroxisome proliferator-activated receptor agonists - Hsiang-Ru Lin (Medicinal Chemistry Research, 2015)

Interaction of DRD2TaqI, COMT, and ALDH2 genes associated with bipolar II disorder comorbid with anxiety disorders in Han Chinese in Taiwan - Ming-Chuan Hu; Sheng-Yu Lee; Tzu-Yun Wang; Yun-Hsuan Chang; Shiou-Lan Chen; Shih-Heng Chen; Chun-Hsien Chu; Chen-Lin Wang; I Hui Lee; Po See Chen; Yen Kuang Yang; Ru-Band Lu (Metabolic Brain Disease, 2015)

Cell-density-dependent manifestation of partial characteristics for neuronal precursors in a newly established human gliosarcoma cell line - Pei-Sen Yao; De-Zhi Kang; Xing-Fu Wang; Ru-Ying Lin; Zu-Cheng Ye (In Vitro Cellular & Developmental Biology - Animal, 2015)

Studies on mitogen-activated protein kinase signaling pathway in the alveolar macrophages of chronic bronchitis rats - Yan Huang; Xiao-Ming Meng; Guo-Lin Jiang; Ya-Ru Yang; Juan Liu; Xiong-Wen Lv; Jun Li (Molecular and Cellular Biochemistry, 2015)

Antimicrobial peptide GW-H1-induced apoptosis of human gastric cancer AGS cell line is enhanced by suppression of autophagy - Wei-Ru Pan; Yi-Lin Sophia Chen; Hui-Chen Hsu; Wei-Jung Chen (Molecular and Cellular Biochemistry, 2015)

Is abnormal non-high-density lipoprotein cholesterol a gender-specific predictor for metabolic syndrome in patients with schizophrenia taking second-generation antipsychotics? - Esther Ching-Lan Lin; Wen-Chuan Shao; Hsin-Ju Yang; Miaofen Yen; Sheng-Yu Lee; Pei-Chun Wu; Ru-Band Lu (Metabolic Brain Disease, 2015)

Compounds from marine-derived Verrucosispora sp. FIM06054 and their potential antitumour activities - Nie Yi-Lei; Wu Yun-Dan; Wang Chuan-Xi; Lin Ru; Xie Yang; Fang Dong-Sheng; Jiang Hong; Lian Yun-Yang (Natural Product Research, 2014)

A study of shear strength properties of municipal solid waste in Chongqing landfill, China - Yan Ru Zhao; Qiang Xie; Gui Lin Wang; Yong Jian Zhang; Yong Xing Zhang; Wenjun Su (Environmental Science and Pollution Research, 2014)

Non-pulmonary vein foci induced before and after pulmonary vein isolation in patients undergoing ablation therapy for paroxysmal atrial fibrillation: incidence and clinical outcome - Hui Cheng; Yin-yin Dai; Ru-hong Jiang; Qiang Liu; Ya-xun Sun; Jian-wei Lin; Zu-wen Zhang; Shi-quan Chen; Jun Zhu; Xia Sheng; Chen-yang Jiang (Journal of Zhejiang University-SCIENCE B, 2014)

Spatial-temporal scales of Green Island wake due to passing of the Kuroshio current - Shih-Jen Huang; Chung-Ru Ho; Sheng-Lin Lin; Shin-Jye Liang (International Journal of Remote Sensing, 2014)

Genome characterization of sugarcane yellow leaf virus from China reveals a novel recombinant genotype - Yi-Hua Lin; San-Ji Gao; Mona B. Damaj; Hua-Ying Fu; Ru-Kai Chen; T. Erik Mirkov (Archives of Virology, 2014)

Effect of copper-induced oxidative stress on sclerotial differentiation and antioxidant properties of Penicillium thomii PT95 strain - Ze-Qing Zhang; Wen-Jing Zhao; Dan-Dan Long; Lin-Ru Niu; Jian-Rong Han (World Journal of Microbiology and Biotechnology, 2014)

Comparison of fatty acid and amino acid profiles of steamed Chinese mitten crab - Yan-Ru Guo; Sai-Qi Gu; Xi-Chang Wang; Lin-Min Zhao; Jin-Yuan Zheng (Fisheries Science, 2014)

Characterization of S-(+)-linalool synthase from several provenances of Cinnamomum osmophloeum - Yan-Liang Lin; Yi-Ru Lee; Wen-Ke Huang; Shang-Tzen Chang; Fang-Hua Chu (Tree Genetics & Genomes, 2014)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

A new sesquiterpene lactone from Sarcandra glabra - Xiao-Ru Hu; Hai-Feng Wu; Xiao-Po Zhang; Jun-Shan Yang; Zhong Dai; Rui-Chao Lin; Xu-Dong Xu (Natural Product Research, 2013)

Identification of liver X receptor and farnesoid X receptor dual agonists from Tithonia diversifolia - Hsiang-Ru Lin (Medicinal Chemistry Research, 2013)

Inhibition of formyl peptide-stimulated phospholipase D activation by Fal-002-2 via blockade of the Arf6, RhoA and protein kinase C signaling pathways in rat neutrophils - Ya-Ru Tsai; Li-Jiau Huang; Hui-Yi Lin; Yun-Jie Hung; Miau-Rong Lee; Sheng-Chu Kuo; Mei-Feng Hsu; Jih-Pyang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Analysis of B-Class Genes NAP3L3 and NAP3L4 in Narcissus tazetta var. chinensis - Xiao-Fang Li; Jing Xu; Ru Yang; Lin-Yan Jia; Xin-Jie Deng; Li-Jun Xiong; Xue-Ping Zhang; Qi Fang; Wei Zhang; Yue Sun; Ling Xu (Plant Molecular Biology Reporter, 2013)

SIRT1 interacts with metabolic transcriptional factors in the pancreas of insulin-resistant and calorie-restricted rats - Yong-Ru Chen; Yu-lin Lai; Shao-da Lin; Xi-tao Li; Yu-Cai Fu; Wen-Can Xu (Molecular Biology Reports, 2013)

Spatio-temporal variation of landscape heterogeneity under influence of human activities in Xiamen City of China in recent decade - Yixiong Huang; Xiuqin Yin; Gongfu Ye; Jiemin Lin; Ru Huang; Na Wang; Liang Wang; Yue Sun (Chinese Geographical Science, 2013)

Concurrent use of antiplatelets, anticoagulants, or digoxin with Chinese medications: a population-based cohort study - Hsin-Hui Tsai; Hsiang-Wen Lin; Chun-Ru Chien; Tsai-Chung Li (European Journal of Clinical Pharmacology, 2013)

Oyster shell reduces PAHs and particulate matter from incense burning - Chi-Ru Yang; Tzu-Hsing Ko; Yuan-Chung Lin; Suen-Zone Lee; Yih-Feng Chang; Hsin-Ta Hsueh (Environmental Chemistry Letters, 2013)

β2-Glycoprotein I inhibits VEGF-induced endothelial cell growth and migration via suppressing phosphorylation of VEGFR2, ERK1/2, and Akt - Wen-Chin Chiu; Jan-Yu Lin; Tzong-Shyuan Lee; Li-Ru You; An-Na Chiang (Molecular and Cellular Biochemistry, 2013)

A Mucormycosis Case in a Cirrhotic Patient Successfully Treated with Posaconazole and Review of Published Literature - Shang-Yi Lin; Po-Liang Lu; Kun-Bow Tsai; Chun-Yu Lin; Wei-Ru Lin; Tun-Chieh Chen; Ya-Ting Chang; Chung-Hao Huang; Chi-Yu Chen; Chung-Chih Lai; Yen-Hsu Chen (Mycopathologia, 2012)

Coupled dynamics of energy budget and population growth of tilapia in response to pulsed waterborne copper - Wei-Yu Chen; Chia-Jung Lin; Yun-Ru Ju; Jeng-Wei Tsai; Chung-Min Liao (Ecotoxicology, 2012)

Molecular characterization and phylogenetic analysis of Sugarcane yellow leaf virus isolates from China - San-Ji Gao; Yi-Hua Lin; Yong-Bao Pan; Mona B. Damaj; Qin-Nan Wang; T. Erik Mirkov; Ru-Kai Chen (Virus Genes, 2012)

The mitochondrial genome of the quiet-calling katydids, Xizicus fascipes (Orthoptera: Tettigoniidae: Meconematinae) - MING RU YANG; ZHI JUN ZHOU; YAN LIN CHANG; LE HONG ZHAO (Journal of Genetics, 2012)

Availability of dopamine and serotonin transporters in opioid-dependent users—a two-isotope SPECT study - Tzung Lieh Yeh; Kao Chin Chen; Shih-Hsien Lin; I. Hui Lee; Po See Chen; Wei Jen Yao; Sheng-Yu Lee; Yen Kuang Yang; Ru-Band Lu; Mei-Hsiu Liao; Nan-Tsing Chiu (Psychopharmacology, 2012)

An upstream regulatory element confers orientation-independent enhancement of the TSG101 promoter activity in transformed cells - Shih-Fang Hsu; Yih-Gang Goan; Hsien-Yu Tsai; Yi-Ru Lin; Rue-Tsuan Liu; Jiin-Tsuey Cheng (Molecular Biology Reports, 2012)

Construction and characterization of a normalized cDNA library from the river snail Bellamya aeruginosa after exposure to copper - Zi-Cheng Li; Li-Hui An; Qing Fu; Ying Liu; Lei Zhang; Hao Chen; Xing-Ru Zhao; Li-Jing Wang; Bing-Hui Zheng; Lin-Bo Zhang (Ecotoxicology, 2012)

Variability of sea surface temperature and warm pool area in the South China Sea and its relationship to the western Pacific warm pool - Chun-Yi Lin; Chung-Ru Ho; Quanan Zheng; Shih-Jen Huang; Nan-Jung Kuo (Journal of Oceanography, 2011)

Estimation of nested spatial patterns and seasonal variation in the longitudinal distribution of Sicyopterus japonicus in the Datuan Stream, Taiwan by using geostatistical methods - Yu-Pin Lin; Cheng-Long Wang; Chi-Ru Chang; Hsiao-Hsuan Yu (Environmental Monitoring and Assessment, 2011)

Assessing abalone growth inhibition risk to cadmium and silver by linking toxicokinetics/toxicodynamics and subcellular partitioning - Wei-Yu Chen; Yun-Ru Ju; Bo-Ching Chen; Jeng-Wei Tsai; Chia-Jung Lin; Chung-Min Liao (Ecotoxicology, 2011)

Lipopolysaccharide-stimulated activation of murine DC2.4 cells is attenuated by n-butylidenephthalide through suppression of the NF-κB pathway - Ru-Huei Fu; Horng-Jyh Hran; Ching-Liang Chu; Chin-Mao Huang; Shih-Ping Liu; Yu-Chi Wang; Ya-Hsien Lin; Woei-Cherng Shyu; Shinn-Zong Lin (Biotechnology Letters, 2011)

Loudness dependence of auditory evoked potentials (LDAEP) correlates with the availability of dopamine transporters and serotonin transporters in healthy volunteers—a two isotopes SPECT study - I Hui Lee; Yen Kuang Yang; Po See Chen; Hui Chun Huang; Tzung Lieh Yeh; Ru-Band Lu; Nan-Tsing Chiu; Wei Jen Yao; Shih-Hsien Lin (Psychopharmacology, 2011)

Asialoglycoprotein receptor interacts with the preS1 domain of hepatitis B virus in vivo and in vitro - Xi Zhang; Shu-mei Lin; Tian-yan Chen; Min Liu; Feng Ye; Yun-ru Chen; Lei Shi; Ying-li He; Lie-xiu Wu; Shu-qin Zheng; Ying-ren Zhao; Shu-lin Zhang (Archives of Virology, 2011)

Establishment of a transgene expression system for the marine microalga Schizochytrium by 18S rDNA-targeted homologous recombination - Ru-Bin Cheng; Xiang-Zhi Lin; Zhao-Kai Wang; Shan-Jun Yang; Hui Rong; Yong Ma (World Journal of Microbiology and Biotechnology, 2011)

PTEN status is related to cell proliferation and self-renewal independent of CD133 phenotype in the glioma-initiating cells - Ru-Bin Cheng; Rui-Juan Ma; Zhao-Kai Wang; Shan-Jun Yang; Xiang-Zhi Lin; Hui Rong; Yong Ma (Molecular and Cellular Biochemistry, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Rubellimicrobium roseum sp. nov., a Gram-negative bacterium isolated from the forest soil sample - Yan-Ru Cao; Yi Jiang; Qian Wang; Shu-Kun Tang; Wen-Xiang He; Quan-Hong Xue; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2010)

The CAG repeat in SCA12 functions as a cis element to up-regulate PPP2R2B expression - Chih-Hsin Lin; Chiung-Mei Chen; Yi-Ting Hou; Yih-Ru Wu; Hsiu-Mei Hsieh-Li; Ming-Tsan Su; Guey-Jen Lee-Chen (Human Genetics, 2010)

Livin abrogates apoptosis of SPC-A1 cell by regulating JNKI signaling pathway - Yu-Sheng Chen; Hong-Ru Li; Ming Lin; Gang Chen; Bao-Song Xie; Neng-Luan Xu; Li-Fang Lin (Molecular Biology Reports, 2010)

Estimates of individuals exposed to human metapneumovirus in a community-based Taiwanese population in 1999 - Chung-Guei Huang; Kuo-Chien Tsao; Tzou-Yien Lin; Yhu-Chering Huang; Li-Ang Lee; Tzu-Hou Chen; Ya-Ling Huang; Shin-Ru Shih (Archives of Virology, 2010)

Genesis and stability of the Zhoujiawan landslide, Three Gorges, China - Wen-jie Xu; Rui-lin Hu; Zhong-qi Yue; Ru-jiao Tan (Bulletin of Engineering Geology and the Environment, 2009)

Human mesenchymal stem cells-like cells as cellular vehicles for delivery of immunotoxin in vitro - Chang-chen Hu; Yi-quan Ke; Xin-lin Sun; Xiao-dan Jiang; Ru-xiang Xu; Jun Lv; Yu-sheng Wang; Ying-qian Cai; Ling-sha Qin; Yu-xi Zou (Biotechnology Letters, 2009)

Effects of ginkgolide B on neuronal discharges in paraventricular nucleus of rat hypothalamic slices - Yue Lin; Ru Wang; Xin Wang; Rui-Rong He; Yu-Ming Wu (Neuroscience Bulletin, 2008)

The Influence of Center of Rotation on the Assessment of Trabecular Bone Densitometric and Structural Properties - Zhi-Feng Sheng; Ru-Chun Dai; Xian-Ping Wu; Yu-Lin Ma; Kang Xu; Yu-Hai Zhang; Ye-Bin Jiang; Er-Yuan Liao (Annals of Biomedical Engineering, 2008)

Improved biodesulfurization of hydrodesulfurized diesel oil using Rhodococcus erythropolis and Gordonia sp. - Guo-Qiang Li; Shan-Shan Li; Shi-Wei Qu; Qing-Kun Liu; Ting Ma; Lin Zhu; Feng-Lai Liang; Ru-Lin Liu (Biotechnology Letters, 2008)

Compositions and source apportionments of atmospheric aerosol during Asian dust storm and local pollution in central Taiwan - Man-Ting Cheng; Wei-Chun Chou; Chia-Pin Chio; Shih-Chieh Hsu; Yi-Ru Su; Pei-Hsuan Kuo; Ben-Jei Tsuang; Shuen-Hsin Lin; Charles C.-K. Chou (Journal of Atmospheric Chemistry, 2008)

Juvenile Tilapia (Oreochromis mossambicus) Strive to Maintain Physiological Functions After Waterborne Copper Exposure - Su Mei Wu; Hui Ru Ding; Li-Yih Lin; Yu-Siang Lin (Archives of Environmental Contamination and Toxicology, 2008)

Early developmental and stress responsive ESTs from mungbean, Vigna radiata (L.) Wilczek, seedlings - Li-Ru Chen; Albert H. Markhart; S. Shanmugasundaram; Tsai-Yun Lin (Plant Cell Reports, 2008)

Exsolution lamellae in a clinopyroxene megacryst aggregate from Cenozoic basalt, Leizhou Peninsula, South China: petrography and chemical evolution - Xiao-Long Huang; Yi-Gang Xu; Ching-Hua Lo; Ru-Cheng Wang; Chuan-Yong Lin (Contributions to Mineralogy and Petrology, 2007)

Glutathione S-transferases M1 and T1 polymorphisms and arsenic content in hair and urine in two ethnic clans exposed to indoor combustion of high arsenic coal in Southwest Guizhou, China - Guo-fang Lin; Hui Du; Ji-gang Chen; Hong-chao Lu; Jin-xiang Kai; Yun-shu Zhou; Wei-chao Guo; Xin-jiang Zhang; Da-ru Lu; Klaus Golka; Jian-hua Shen (Archives of Toxicology, 2007)

Isolation and characterization of a novel thermophilic Bacillus strain degrading long-chain n-alkanes - Lei Wang; Yun Tang; Shuo Wang; Ru-Lin Liu; Mu-Zhi Liu; Yan Zhang; Feng-Lai Liang; Lu Feng (Extremophiles, 2006)

Roots of pioneer trees in the lower sub-tropical area of Dinghushan, Guangdong, China - Yan-ru Hao; Shao-lin Peng; Jiang-ming Mo; Xin-wei Liu; Zhuo-quan Chen; Kai Zhou; Jin-rong Wu (Journal of Zhejiang University-SCIENCE B, 2006)

Identifying the Scale Thresholds for Field-Data Extrapolation via Spatial Analysis of Landscape Gradients - Chi-Ru Chang; Pei-Fen Lee; Mei-Ling Bai; Tzer-Ton Lin (Ecosystems, 2006)

TransgenicLycium barbarum L. Established as HIV capsid protein expression system - Guo-Li Du; Chang-Zheng Song; Geng-Lin Zhang; Xiao-Guang Sun; Dan-Ru Liu (Plant Molecular Biology Reporter, 2005)

An efficient protocol for plant regeneration from protoplasts of the moss Atrichum undulatum P. Beauv in vitro - Lin-Hui Li; Xian-Ping Wang; Wan-Ru Hou; Xiang-Lin Liu; Yi-Kun He (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Histidines 345 and 378 of Bacillus stearotheromophilus leucine aminopeptidase II are essential for the catalytic activity of the enzyme - Guang-Yuh Hwang; Lih-Ying Kuo; Ming-Ru Tsai; Shin-Ling Yang; Long-Liu Lin (Antonie van Leeuwenhoek, 2005)

Analysis of heat-shock protein70 gene polymorphisms and the risk of Parkinson?s disease - Chiung-Mei Chen; Yuying Hsu; Sih-Jing Lin; Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Cheng-Kuang Wang; Yi-Ying Lin; Yih-Ru Wu; Hon-Chung Fung (Human Genetics, 2004)

Diverse apoptotic pathways in enterovirus 71–infected cells - Shih-Cheng Chang; Jing-Yi Lin; Lily Yen-Cheng Lo; Mei-Ling Li; Shin-Ru Shih (Journal of NeuroVirology, 2004)

Identification of genes involved in the host response to enterovirus 71 infection - Shin-Ru Shih; Victor Stollar; Jing-Yi Lin; Shih-Cheng Chang; Guang-Wu Chen; Mei-Ling Li (Journal of NeuroVirology, 2004)